Nanoparticles
By forming an outer layer structure of a variety of metal cations and divalent anions on the semiconductor nanoparticles, the shell composition and dynamics are optimized, and the particle size distribution, quantum yield and stability of semiconductor nanoparticles in the prior art are solved. A more efficient charge injection and a more environmentally friendly manufacturing process are achieved.
Patent Information
- Application Number
- CN202080030550.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-26
- Filing Date
- 2020-04-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-04-23
AI Technical Summary
The prior art has problems such as uneven particle size distribution, low self-absorbing value, poor quantum yield, insufficient charge injection capacity, poor thermal and chemical stability, many shell lattice defects, and unenvironmental manufacturing process when preparing semiconductor nanoparticles. .
Using semiconductor nanoparticles with outer structures containing metal cations and divalent anions, the outer layer is formed in the range of 80°C to 200°C by specific chemical reaction methods, and using a variety of metal cations and divalent anions combinations to optimize the shell. Composition and kinetics, using environmentally friendly solvents and processes.
The particle size distribution, self-absorbing value, quantum yield, charge injection capability and stability of nanoparticles are improved, the lattice defects of the shell and the environmental impact of the manufacturing process are reduced, and the device efficiency and safety are improved.
Smart Images

Figure CN113728073B_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to nanoparticles; a method for preparing nanoparticles; a composition of nanoparticles, a preparation of nanoparticles, and uses of nanoparticles; an optical medium; and an optical device. Background Art
[0002] Luminescent nanoparticles are known in the prior art literature.
[0003] For example, Turo et al., ACS NANO, Vol. 8, No. 10, 10205-10203, 2014, discloses Cu2S nanoparticles without a shell layer having dodecanethiol (DDT) and a manufacturing process using DDT at a temperature of 200° C. DDT was used throughout the synthesis process.
[0004] Turo et al., Chem Commun, 2016, 52, 12214-12217, describe CdSe / ZnS with dodecanethiol.
[0005] Robinson et al., Chem Mater, 2017, 29, 3854-3857 mentioned quasi-spherical Cu2S nanorods with DDT.
[0006] Patent Literature
[0007] No literature
[0008] Non-patent literature
[0009] 1. Turo et al., ACS NANO vol.8, no.10, 10205-10203, 2014
[0010] 2.Chem Commun, 2016, 52, 12214-12217
[0011] 3. Robinson et al., Chem Mater, 2017, 29, 3854-3857 SUMMARY OF THE INVENTION
[0013] However, the inventors have newly found that there are still one or more significant problems that need to be improved, as listed below: improvement in particle size distribution, better full width at half maximum (FWHM) value, improved self-absorption value, improvement in absorption per mg of one or more nanoparticles, improvement in quantum yield of nanoparticles, well-controlled shell thickness, improved charge injection capability of nanoparticles, higher device efficiency, reduction in trap emission of nanoparticles, optimization of the surface conditions of the nanoparticle shell portion, reduction in lattice defects of the nanoparticle shell layer, reduction / prevention of the formation of dangling bonds in the shell layer, better thermal stability, better chemical stability, improved chemical stability in one or more desired solvents, chemical stability, improved thermal stability in one or more desired solvents, improved chemical stability in one or more desired matrices, improved thermal stability in one or more desired matrices, improved dispersion in matrices, improved dispersion in solvents, improved hole injection into semiconductor light-emitting nanoparticles, improved external quantum efficiency, optimization of nanoparticle manufacturing processes, provision of new manufacturing processes to improve size control of nanoparticles, provision of new manufacturing processes to better control the kinetics of shell formation, new shell formation processes to achieve well-controlled shell thickness and / or reduce lattice defects in the shell layer, and more environmentally friendly and safer manufacturing processes.
[0014] The present inventors aim to address one or more of the above problems.
[0015] Then a new type of semiconductor nanoparticle, preferably a semiconductor light emitting nanoparticle, comprising, consisting essentially of or consisting of a core, an outer layer comprising metal cations and divalent anions covering at least a portion of said core, and one or more types of organic moieties directly attached to the anions of said outer layer by covalent bonds,
[0016] Wherein the divalent anion is selected from Se 2- , S 2- 、Te 2- O 2- or any combination thereof, preferably, the metal cation is a monovalent, divalent, trivalent or tetravalent cation, more preferably, the metal cation is selected from Zn 2+ 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ A divalent cation, or selected from Ti 4+ ,Ge 4+ 、Si 4+ 、Zr 4+ , Hf 4+ and Sn 4+ of tetravalent cations.
[0017] In some embodiments of the invention, the outer layer comprises at least two or three different metal cations, such as Cu 1+ andIn 3+ ,Cu 1+ and Ga 3+ ,Ag 1+ and Ga 3+ Combination or Cu +1 / In +3 / Zn +2 combination.
[0018] In another aspect, the present invention further relates to a method for producing luminescent nanoparticles, comprising at least the following steps,
[0019] (a) mixing at least one semiconductor nanomaterial with another material to obtain a reaction mixture, preferably, the semiconductor nanoparticles contain at least the first semiconductor nanomaterial as a core, and preferably the another material is a solvent;
[0020] (b) forming an outer layer on the semiconductor nanoparticles in the reaction mixture by reacting at least one anion source represented by chemical formula (Va) or chemical formula (Vb) with a metal cation precursor in the reaction mixture, and in some embodiments of the present invention, the metal cation precursor can be the same as the cationic shell precursor.
[0021] ABXH (Va)
[0022] ABXXBA (Vb)
[0023] in
[0024] A is an organic group;
[0025] B is a connecting unit connecting A and X;
[0026] H is a hydrogen atom; and
[0027] X is an anion-containing anchoring group capable of forming a monolayer with an added metal cation that may be derived from an added metal cation precursor;
[0028] (c) cooling the reaction mixture from step (b),
[0029] The reaction mixture in step (b) is maintained at a temperature in the range of 80°C to 200°C, preferably 100 to 200°C to form the outer layer in step (b).
[0030] In another aspect, the present invention relates to semiconductor nanoparticles or semiconductor luminescent nanoparticles obtainable or obtained by the method of the present invention.
[0031] In another aspect, the present invention also relates to a composition comprising, essentially consisting of or consisting of at least one semiconductor nanoparticle of the present invention and at least one additional material, preferably, the additional material is selected from organic light-emitting materials, inorganic light-emitting materials, charge transport materials, scattering particles, host materials, nanoplasmonic particles, photoinitiators and matrix materials.
[0032] In another aspect, the present invention relates to a formulation comprising, consisting essentially of or consisting of at least one semiconductor nanoparticle of the present invention or a composition of the present invention and at least one solvent, preferably, the solvent is selected from one or more of aromatic, halogenated and aliphatic hydrocarbon solvents, ethers, esters, ionic liquids, alcohols and water, more preferably selected from one or more of toluene, xylene, tetrahydrofuran, chloroform, dichloromethane and heptane, hexane, purified water, acetates, ether acetates, ketones, ether esters such as PGMEA, alcohols such as ethanol, isopropanol, etc., sulfoxides, formamides, nitrides, ketones.
[0033] In another aspect, the present invention relates to the use of semiconductor nanoparticles, compositions or formulations in electronic devices, optical devices, sensor devices or biomedical devices.
[0034] In another aspect, the present invention further relates to an optical medium comprising at least one luminescent nanoparticle, or composition of the present invention.
[0035] In another aspect, the present invention further relates to an optical device comprising at least the optical medium. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 : QDs from working example 1 before (a) and after (b) addition of 3-phenylpropylphosphonic acid (PPPA) 1 H NMR spectrum (in toluene d8).
[0037] Figure 2 : QDs from working example 1 after treatment with PPPA and washing with ethanol 1 H NMR spectrum (in toluene d8).
[0038] Figure 3 : GCMS spectrum of QDs from working example 1 after treatment with PPPA and washing. MS spectrum of the peak with retention time 11.45.
[0039] Figure 4 : A general scheme of the multistep method established to distinguish between surface- and crystal-bound ligands is described, using dodecanediselenol (DDSe) as an example (Scheme 1). DETAILED DESCRIPTION OF THE INVENTION
[0041] -Semiconductor Nanoparticles
[0042] According to the present invention, in one aspect, the semiconductor nanoparticle, preferably a semiconductor luminescent nanoparticle, comprises, consists essentially of or consists of a core, an outer layer comprising metal cations and divalent anions covering at least a portion of the core, and an organic moiety, preferably one or more types of organic moieties directly connected to the anions of the outer layer by covalent bonds,
[0043] Wherein the divalent anion is selected from Se 2- , S 2- 、Te 2- O 2- or any combination thereof, preferably, the metal cation is a monovalent, divalent, trivalent or tetravalent cation, more preferably, the metal cation is selected from Zn 2+ 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ A divalent cation, or selected from Ti 4+ ,Ge 4+ 、Si 4+ 、Zr 4+ , Hf 4+ and Sn 4+ of tetravalent cations.
[0044] The nanoparticles comprise at least an outer layer and a core. The nanoparticles may optionally comprise one or more further layers (shell layers) between the outer layer and the core.
[0045] The outer layer covers at least a portion of the core. If there are no other layers between the outer layer and the core, the outer layer can be in direct physical contact with the core.
[0046] The outer layer may cover the core by one or more additional layers placed between the outer layer and the core.
[0047] The term "covering" and the term "coating" do not necessarily mean that there is always physical contact between the core and the outer layer.
[0048] In some embodiments of the invention, the outer layer comprises at least two or three different metal cations, such as Cu 1+ andIn 3+ ,Cu 1+ and Ga 3+ ,Ag 1+ and Ga 3+ Combination or Cu +1 / In +3 / Zn +2 combination.
[0049] According to the present invention, the term "nanoscopic" means a size of 0.1 nm to 999 nm, preferably 0.5 nm to 150 nm, more preferably 1 nm to 50 nm.
[0050] According to the present invention, the term "semiconductor" means a material having an electrical conductivity at room temperature in a degree between that of a conductor (eg, copper) and an insulator (eg, glass), a semiconductor being a material whose electrical conductivity increases with temperature.
[0051] Therefore, according to the present invention, the term "semiconductor nanoparticles" means a material having an electrical conductivity at room temperature between that of a conductor (e.g., copper) and an insulator (e.g., glass), preferably a semiconductor is a material whose electrical conductivity increases with temperature, and has a size of 0.1 nm to 999 nm, preferably 0.5 nm to 150 nm, and more preferably 1 nm to 50 nm.
[0052] According to the present invention, the term "size" means that the area of the semiconductor nano-luminescent particles is equal to the average diameter of a circle of the measured TEM projection area.
[0053] In a preferred embodiment of the present invention, the semiconductor light-emitting nanoparticles of the present invention are quantum-sized materials.
[0054] According to the present invention, the term "quantum size" means the size of the first semiconductor nanoparticle itself without ligands or other surface modifications, which can show quantum confinement effects, such as described in ISBN: 978-3-662-44822-9.
[0055] Typically, quantum-sized materials can emit tunable, sharp, and vividly colored light due to an effect called "quantum confinement."
[0056] In some embodiments of the present invention, the overall structure of the quantum sized material has a size between 1 nm and 50 nm.
[0057] In a preferred embodiment of the present invention, the average diameter of the first semiconductor nanoparticles (cores) is in the range of 1 to 20 nm, preferably in the range of 1.5 to 12 nm.
[0058] The average diameter of the semiconductor luminescent nanoparticles (cores) was calculated based on 100 semiconductor luminescent nanoparticles in the TEM images taken by a Tecnai G2 Spirit Twin T-12 transmission electron microscope. The average diameter of the semiconductor luminescent nanoparticles was calculated using the Fiji_ImageJ program.
[0059] -Organic part
[0060] In a preferred embodiment of the present invention, the organic moiety is represented by the following chemical formula (I);
[0061] AB-* (I)
[0062] in
[0063] A is an organic group; and
[0064] B is the connection unit;
[0065] The “*” represents the point of attachment to the anion in the outer shell.
[0066] More preferably, the organic moiety is represented by the following chemical formula (II), (III) or (IIIa);
[0067] L-(U) o -(Y) m -(CH2) n -* (II)
[0068] in
[0069] L is an organic group, preferably, the organic group is a hydrocarbon group (alkyl, aryl, aralkyl and alkaryl), a heteroaryl group, including an aryl group, an alkaryl group, an alkyl group or an aralkyl group, an alkylamine, a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group, a fluoroaralkyl group, a heteroaryl group, and the heteroaryl group includes a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group or a fluoroaralkyl group;
[0070] U is O, CH2 or C=O;
[0071] Y is O, CH2 or C=O;
[0072] n is an integer of 1 or greater;
[0073] m is an integer of 0 or 1 or greater, preferably m is 1;
[0074] o is an integer of 0 or 1 or greater, preferably o is 1;
[0075] "*" represents the connection point with the anion in the outer layer, preferably, the anion is selected from Se 2- , S 2- 、Te 2- and O 2- One or more of, more preferably, the organic moiety is covalently bonded to a Se, S, Te or O atom in the outer shell;
[0076] *-(CH2) a -(OCH2CH2) p -(V) r -(CH2) q -Z (III)
[0077] *-(CH2) q -(V) r -(OCH2CH2) p -Z (IIIa)
[0078] in
[0079] V is O, CH2 or C=O;
[0080] Z is a hydrogen atom or an organic group, preferably Z is a hydrogen atom; a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, a branched unsaturated hydrocarbon group having 3 to 30 carbon atoms, or an aromatic hydrocarbon group, such as a straight-chain alkyl group having 1 to 25 carbon atoms, a branched alkyl group having 3 to 25 carbon atoms; -COOH, -SH or -NH2, alkylamine, a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group, a heteroaryl group, the heteroaryl group including a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group or a fluoroalkyl group, preferably Z is a hydrogen atom, a straight-chain alkyl group having 1 to 25 carbon atoms, a branched alkyl group having 3 to 25 carbon atoms, more preferably it is a hydrogen atom, a straight-chain alkyl group having 1-15 carbon atoms, a branched alkyl group having 3-15 carbon atoms, even more preferably it is a hydrogen atom, or a straight-chain alkyl group having 1-10 carbon atoms;
[0081] a is an integer of 0 or 1 or greater, preferably 0≤a≤25, more preferably 0≤a≤15, even more preferably 1≤a≤10;
[0082] p is an integer of 0 or 1 or greater, preferably 0≤p≤45, more preferably 0≤p≤25, even more preferably 1≤p≤20, further preferably 4≤p≤16;
[0083] q is an integer of 0 or 1 or more, preferably 0≤q≤25, more preferably 0≤q≤15, even more preferably 0≤q≤10, and further preferably 1≤q≤5;
[0084] r is 0 or integer 1;
[0085] "*" represents the connection point with the anion in the outer layer, preferably, the anion is selected from Se 2- , S 2- 、Te 2- and O 2- More preferably, the organic moiety is covalently bonded to a Se, S, Te or O atom in the outer layer.
[0086] Even more preferably, the organic moiety of the present invention is represented by the following chemical formula (IV):
[0087] *-(CH2) a -(OCH2CH2) p -(O) r-(CH2) q -Z′ (IV)
[0088] wherein a is an integer of 0 or 1 or greater, preferably 0≤a≤25, more preferably 0≤a≤15, even more preferably 1≤a≤10;
[0089] p is an integer of 0 or 1 or greater, preferably 0≤p≤45, more preferably 0≤p≤25, even more preferably 1≤p≤20, further preferably 4≤p≤16;
[0090] q is an integer of 0 or 1 or greater, preferably 0≤q≤25, more preferably 0≤q≤15, even more preferably 0≤q≤10, and further preferably 1;
[0091] Z' is a hydrogen atom, a straight-chain alkyl group having 1 to 25 carbon atoms, a branched-chain alkyl group having 3 to 25 carbon atoms, an alkylamine, a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group, a fluoroaralkyl group, a heteroaryl group, wherein the heteroaryl group includes a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group or a fluoroaralkyl group, preferably Z' is a straight-chain alkyl group having 1 to 25 carbon atoms, a branched-chain alkyl group having 3 to 25 carbon atoms or a hydrogen atom, more preferably a straight-chain alkyl group having 1-15 carbon atoms, a branched-chain alkyl group having 3-15 carbon atoms or a hydrogen atom, and even more preferably a hydrogen atom;
[0092] r is 0 or integer 1;
[0093] "*" indicates a connection point to an anion in the outer shell, preferably a connection point to a S atom or a Se atom in the outer shell.
[0094] More preferably, the organic moiety is *-(CH2)2-(OCH2CH2) 5≤p≤20 -O-CH3, more preferably *-(CH2)2-(OCH2CH2)6-O-CH3 and / or *-(CH2)2-(OCH2CH2) connected to a S atom or a Se atom in the outer shell 16 -O-CH3.
[0095] In some preferred embodiments, the organic moiety is CH3-(CH2) 7<n<18 -* and connected to the S or Se atom in the outer shell.
[0096] In a preferred embodiment of the present invention, the organic moiety selected from formula (I), (II), (III), (III') or (IV) is covalently bound to an anion in the outer inorganic lattice, preferably without being removed by ligand exchange.
[0097] Crystal binding ligands (covalently bound ligands) can be characterized as described in working Example 7.
[0098] For example, the organic part may preferably be described as follows:
[0099] *-CH2-(OCH2CH2)4-O-CH3
[0100] *-CH2-(OCH2CH2)6-O-CH3
[0101] *-CH2-(OCH2CH2)8-O-CH3
[0102] *-(CH2)2-(OCH2CH2)2-O-CH3
[0103] *-(CH2)2-(OCH2CH2)6-O-CH3
[0104] *-(CH2)2-(OCH2CH2)8-O-CH3
[0105] *-(CH2)2-(OCH2CH2)6-CH3
[0106] *-(CH2)2-(OCH2CH2)6-O-(CH2)2-SH
[0107] *-(CH2) 7- CH3
[0108] *-(CH2) 11- CH3
[0109] *-(CH2) 17- CH3
[0110] *-(CH2)2-(OCH2CH2)6-O-CH3
[0111] *-(CH2)2-(OCH2CH2) 16 -O-CH3
[0112] *-(CH2)2-(OCH2CH2) 17 -O-CH3
[0113] "*" represents the point of connection to an S atom or a Se atom in the outer shell; or
[0114] *-(CH2) 11- CH3;
[0115] "*" represents the connection point to the S atom or Se atom in the outer layer.
[0116] In some embodiments, the organic moiety of the chemical formula (I) or (II) may be an organic moiety represented by the following chemical formula Ia, Ib, Ic, Id, Ie, IIa, IIb, IIc, IId, IIe, IIf, IIg, IIh, IIi or IIj;
[0117]
[0118]
[0119] wherein Y is a binding unit having two binding moieties, m is 0 or 1, R 6 is a hydrogen atom or R 1 , R 7 is a hydrogen atom or R 1 .
[0120] R 1 and R 5 is, at each occurrence, independently or dependently, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 5 to 12 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, a cycloalkenyl group having 5 to 12 carbon atoms, an aralkyl group having 7 to 15 carbon atoms, a saturated or unsaturated bicyclic or tricyclic hydrocarbon group having 7 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms or said aryl group substituted by an alkyl group, or OR x ;
[0121] R x is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 5 to 12 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, a cycloalkenyl group having 5 to 12 carbon atoms, an aralkyl group having 7 to 15 carbon atoms, a saturated or unsaturated bicyclic or tricyclic hydrocarbon group having 7 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms, or said aryl group substituted with an alkyl group;
[0122] R 2 is a hydrogen atom or R 3 ;
[0123] R a is an alkyl group having 1 to 36 carbon atoms, preferably selected from the group consisting of methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, tetradecyl, hexadecyl, eicosyl, docosyl, pentacosyl, heptacosyl, triacontyl, dotriacontyl, tetratriacontyl, hexatriacontyl and branched chain isomers thereof;
[0124] R 3 is a cycloalkyl group having 5 to 12 carbon atoms, a phenyl group or a naphthyl group which is unsubstituted or substituted with an alkyl group having 1 to 36 carbon atoms, or an aralkyl group having 7 to 9 carbon atoms which is unsubstituted or substituted with an alkyl group having 1 to 36 carbon atoms;
[0125] R 4 is an alkyl group having 1 to 36 carbon atoms, preferably selected from the group consisting of methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, tetradecyl, hexadecyl, eicosyl, docosyl, pentacosyl, heptacosyl, triacontyl, dotriacontyl, tetratriacontyl, hexatriacontyl and branched chain isomers thereof;
[0126] R 6 is a hydrogen atom or R 1 ;
[0127] R 7 is a hydrogen atom or R 1 ;
[0128] "*" indicates the connection point with the anion in the outer layer, preferably, the anion is selected from Se 2- , S 2- , O 2- and Te 2- One or more, more preferably organic moieties are bonded to Se, S, O or Te atoms in the outer layer;
[0129] n is zero or an integer;
[0130]
[0131] in
[0132] Z is a binding unit having two binding parts, preferably selected from a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted oxyalkylene group having 1 to 10 carbon atoms;
[0133] Y is the connection unit;
[0134] m is 0 or 1;
[0135] R 6 is a hydrogen atom or R 1 ;
[0136] R 7 is a hydrogen atom or R 1 ;
[0137] R 8 OH, hydrogen atom or R 1 ;
[0138] R 9 OH, hydrogen atom or R 1 ;
[0139] R 10 is a hydrogen atom or R 1 ;
[0140] R 11 OH, hydrogen atom or R 1 ;
[0141] R 12 is a hydrogen atom or R 1 ;
[0142] In some embodiments, the organic moiety represented by formula II) is an organic moiety represented by IIa, IIb, IIc, IId, IIe, IIf, IIg, IIh, IIi, or IIj;
[0143]
[0144]
[0145]
[0146] "*" represents the point of attachment to the anion in the outer shell, preferably the organic moiety of formula IIa, IIb, IIc, IId, IIe, IIf, IIg, IIh, IIi or IIj is bound to a Se, S or Te or O atom in the outer shell;
[0147] n is zero or an integer.
[0148] In some embodiments, the organic moiety has a biological function.
[0149] In some embodiments, the ligand is bifunctional, allowing the nanoparticle to bind to a specific site.
[0150] It is believed that the organic portion prevents aggregation of the nanoparticles or nano-sized materials and that the organic portion allows for dispersion of the nanoparticles in an organic medium and / or an aqueous medium.
[0151] It is also believed that the organic portion allows for increased cellular uptake.
[0152] In some embodiments, the organic moiety is similar to the structure described below:
[0153] 1.Chemistry&Biology 18,January 28,2011,10-24,
[0154] 2.J.Am.Chem.Soc.,2007,129(45),pp 13987–13996,
[0155] 3.Materials Today, Vol. 20, Issue 7, 2017, pp. 360-376.
[0156] In some embodiments, the organic moiety comprises a protein or a protein building block.
[0157] In some embodiments, the organic moiety comprises a zwitterionic group.
[0158] -nuclear
[0159] According to the present invention, the semiconductor nanoparticles include a core, which can be made of several semiconductor materials, for example, CdS, CdSe, CdTe, ZnS, ZnSe, ZnSeS, ZnTe, ZnO, GaAs, GaP, GaSb, CuS, Cu2S, CuSe, Cu2Se, FeS, FeSe, FeO, FeTe, HgS, HgSe, HgSe, HgTe, InAs, InxGa1-xAs, InP, InP:Zn, InP:ZnS, InP:ZnSe, InP:ZnSSe, InP:Ga, or InP: Ga, InSb, InPS, InPZnS, InPSe, InPZn, InPZnSe, InPZnSeS, InPGa, InPGaZn, InP / ZnSe, In / ZnS, InZn P / ZnSe, InP / ZnSeTe, InZnP / ZnSeTe, InGaP / ZnSe, InP / InGaP, InZnP / InGaP, InCdP, InPCdS, InP / ZnSeS, I nZnP / ZnSeS, InZnP / ZnS, InZnP / InGaP / ZnSe, InZnP / InGaP / ZnS, InZnP / InGaP / ZnSeS, InPCdSe, InGaP, InGaPZn, PbSe, PbS, InSb, AlAs, AlP, AlSb, CuInS2, CuInSe2, CuInZnSe, CuInZnS, AgInS2, TiO2 and any combination of these.
[0160] In some embodiments of the present invention, the core comprises at least a first element of Group 12 or 13 of the periodic table and a second element of Group 15 or 16 of the periodic table, preferably, the first element is an element of Group 13 of the periodic table and the second element is an element of Group 15 of the periodic table, more preferably, the first element is a combination of In and Ga, and the second element is P.
[0161] In a preferred embodiment of the present invention, the first core may further include an additional element selected from one or more members of Ga, Zn, S and Se.
[0162] In some embodiments, the core is a metal oxide, including, for example, ZnO, FeO, Fe2O3, ZrO2, CuO, SnOCu2O, TiO2, WO 3、 HkDJ 2、 In2O 3、 MgO, Al2O3 and any combination of these.
[0163] In some embodiments, the core comprises a metal such as Au, Ag, W, Pd, Pt, Cu, In, Ti, Zn, Pb, Al, Cd, Zn, and combinations of any of these.
[0164] In a preferred embodiment of the present invention, the first semiconductor nanomaterial is selected from InP, InP:Zn, InP:ZnS, InP:ZnSe, InP:ZnSSe, InP:Ga or InP:GaZn, InP / ZnSe, InP / ZnS, InP / ZnSeS, InZnP / ZnSe, InZnP / ZnSeS, InZnP / ZnS, InGaP / ZnSe, InP / InGaP, InZnP / InGaP, InZnP / InGaP / ZnSe, InZnP / InGaP / InZnP, InZnP / InGaP / ZnS, InZnP / InGaP / ZnSeS.
[0165] According to the present invention, the shape type of the first semiconductor nanomaterial of the semiconductor nanoparticles and the shape of the semiconductor light-emitting nanoparticles to be synthesized are not particularly limited.
[0166] For example, spherical, elongated, star-shaped, polyhedral, pyramidal, multi-podal such as tetrapodal, tetrahedral, platelet-shaped, cone-shaped and irregular first semiconductor nano-sized materials and-or semiconductor light-emitting materials can be used.
[0167] In some embodiments of the present invention, the average diameter of the core is in the range of 1 to 20 nm, preferably 1 to 12 nm, more preferably 1.5 nm to 7 nm.
[0168] -Outer layer
[0169] According to the invention, the semiconductor nanoparticle comprises an outer layer covering at least a portion of the core, the outer layer comprising at least one metal cation and at least one divalent anion,
[0170] Wherein the divalent anion is selected from Se 2- , S 2- 、Te 2- O 2- or any combination thereof, preferably, the metal cation is a monovalent, divalent, trivalent or tetravalent cation, more preferably the metal cation is selected from Zn 2+ 、Ni2+ 、Co 2+ , Ca 2+ , Sr 2+ , Fe 2+ , Hg 2+ Mg 2+ and Pb 2+ Divalent cations, or selected from Ti 4+ ,Ge 4+ 、Si 4+ 、Zr 4+ , Hf 4+ and Sn 4+ The tetravalent cation
[0171] In some embodiments, the cation is selected from Cs + 、Ag + 、Au + , Cu +1 A monovalent cation or selected from Zn 2+ , Fe +2 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ , Cu +2 A divalent cation or selected from Fe +3 、In +3 、Bi +3 , Ga +3 The trivalent cation is selected from Ti 4+ ,Ge 4+ 、Si 4+ 、Zr 4+ , Hf 4+ and Sn 4+ 、Si +4 of tetravalent cations.
[0172] In some embodiments of the invention, the outer layer comprises at least two or three different metal cations, such as Cu 1+ andIn 3+ , Cu 1+ and Ga 3+ 、Ag 1+ and Ga 3+ Combination or Cu +1 / In +3 / Zn +2 Combination or Cu +1 / Ga +3 / Zn +2 Combination or Cu +1 / In +3 / Ga +3 / Zn +2 Combination or Cu +1 / In +3 / Ga +3 combination.
[0173] In a preferred embodiment, the metal cation is selected from Fe +2 、Zn 2+ 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ , Cu +2 of divalent cations.
[0174] In a preferred embodiment of the present invention, the outer layer comprises, consists essentially of or consists of a material represented by the following chemical formula (VI),
[0175] QP 1-2h A h (VI)
[0176] Wherein Q is selected from Se 2- , S 2- 、Te 2- and O 2- A divalent anion of one or more members of
[0177] P is a divalent metal cation, preferably P is selected from Zn 2+ 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ A divalent cation of one or more members of;
[0178] A is a tetravalent cation, preferably A is selected from Ti 4+ ,Ge 4+ 、Si 4+ and Sn 4+ one or more members of; and
[0179] 0≤h≤0.5.
[0180] For example, ZnS, ZnSe, ZnSeS, ZnTe, ZnO, ZnNiS, ZnNiSe, ZnGeS, ZnGeO, ZnCaS, NiSe, TiGeSeS, ZnTiS, CuInZnS, CuInZnSe, AgInZnS and / or AgInZnSe may be used.
[0181] According to the present invention, preferably, the outer layer is a single layer.
[0182] More preferably, it is the last monolayer of the semiconductor nanoparticle covering the core. If there are one or more shell layers covering the core, the outer layer covers the shell layer.
[0183] -Shell
[0184] According to the present invention, in some embodiments, the core can be at least partially embedded in the first shell, preferably, the core is completely embedded in one or more shells. In a preferred embodiment of the present invention, the shell (one or more) is located between the core and the outer layer. In other words, the semiconductor light-emitting nanoparticles of the present invention can optionally sequentially comprise, essentially consist of or consist of a core, one or more shells covering the core, and an outer layer covering the shell.
[0185] -First Shell
[0186] In some embodiments of the present invention, the shell layer comprises at least one metal cation and at least one divalent anion as described in the outer layer portion and / or at least one 1st element of Group 12 of the Periodic Table and Se atom or S atom, preferably, the 1st element is Zn.
[0187] For example, the first shell layer is selected from Cs2S, Cs2Se, Cs2Te, Cs2O, Ag2S, Ag2Se, Ag2Te, Ag2O, Au2S, Au2Se, Au2Te, Au2O, Cu2S, Cu2Se, Cu2Te, Cu2O, ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, CaS, CaSe, CaTe, CaO, NiS , NiSe, NiTe, NiO, MgS, MgSe, MgTe, MgO, HgS, HgSe, HgTe, HgO, PbS, PbSe, PbTe, PbO, CuS, CuSe, CuTe, CuO, CoS, CoSe, CoTe, CoO, SrO, SrS, SrSe, CoTe, SrO, FeS, FeSe, FeO, FeTe, In2S3, In2Se3 , In2Te3, In2O3, Ga2S3, Ga2Se3, Ga2Te3, Ga2O3, Bi2S3, Bi2Se3, Bi2Te3, Bi2O3, Fe2S3, Fe2Se3, Fe2Te3, Fe2O3, TiS2, TiSe2, TiTe2, TiO2, SiS2, SiSe2, SiTe2, SiO2, ZrS2, ZrSe2, ZrTe2, ZrO2, HfS2, HfSe2, HfTe2, HfO2, SnS2, SnSe2, SnTe2, SnO2, GeS2, GeSe2, GeTe2, GeO, CuInZnS, CuInS2, CuInZnSe, CuInSe2, AgInZnS, AgInZnSe, CuGaZnS, CuGaZnSe, CuFeS2, CuFeSe2, and any combination of these.
[0188] Preferably, it is selected from ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, CaS, CaSe, CaTe, CaO, NiS, NiSe, NiTe, NiO, MgS, MgSe, MgTe, MgO, HgS, HgSe, HgTe, HgO, PbS, PbSe, PbTe, PbO, CuS, CuSe, CuTe, CuO, CoS, CoSe, CoTe, CoO, SrO, SrS, SrSe, CoTe, SrO, FeS, FeSe, FeO, FeTe and combinations of any of these materials.
[0189] More preferably: ZnS, ZnSe, ZnTe, ZnO or a combination of any of these materials.
[0190] In a preferred embodiment of the present invention, the first shell layer may be represented by the following formula (VII),
[0191] ZnS x Se (1-x-z) Te z ,-(VII)
[0192] Where 0≤x≤1, 0≤z≤1, and x+z≤1, the preferred shell is ZnSe, ZnS, ZnS x Se (1-x) 、ZnSe (1-x) Te z , more preferably ZnSe or ZnS.
[0193] In some embodiments of the present invention, the shell layer is an alloy shell layer or a gradient shell layer. Preferably, the gradient shell layer is ZnSe, ZnS x Se (1-x) or ZnSe (1-z) Te z , more preferably it is ZnS x Se (1-x) .
[0194] In some embodiments of the present invention, optionally, the first semiconductor nanoparticle as the core and the first shell layer may be at least partially embedded in the second shell, preferably, the first semiconductor nanoparticle is completely embedded in the shell layer.
[0195] For example, the second shell layer is selected from Cs2S, Cs2Se, Cs2Te, Cs2O, Ag2S, Ag2Se, Ag2Te, Ag2O, Au2S, Au2Se, Au2Te, Au2O, Cu2S, Cu2Se, Cu2Te, Cu2O, ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, CaS, CaSe, CaTe, CaO, NiS , NiSe, NiTe, NiO, MgS, MgSe, MgTe, MgO, HgS, HgSe, HgTe, HgO, PbS, PbSe, PbTe, PbO, CuS, CuSe, CuTe, CuO, CoS, CoSe, CoTe, CoO, SrO, SrS, SrSe, CoTe, SrO, FeS, FeSe, FeO, FeTe, In2S3, In2Se3 , In2Te3, In2O3, Ga2S3, Ga2Se3, Ga2Te3, Ga2O3, Bi2S3, Bi2Se3, Bi2Te3, Bi2O3, Fe2S3, Fe2Se3, Fe2Te3, Fe2O3, TiS2, TiSe2, TiTe2, TiO2, SiS2, SiSe2, SiTe2, SiO2, ZrS2, ZrSe2, ZrTe2, ZrO2, HfS2, HfSe2, HfTe2, HfO2, SnS2, SnSe2, SnTe2, SnO2, GeS2, GeSe2, GeTe2, GeO, CuInZnS, CuInS2, CuInZnSe, CuInSe2, AgInZnS, AgInZnSe, CuGaZnS, CuGaZnSe, CuFeS2, CuFeSe2, and any combination of these.
[0196] Preferably, it is selected from ZnS, ZnSe, ZnTe, ZnO, CdS, CdSe, CdTe, CdO, CaS, CaSe, CaTe, CaO, NiS, NiSe, NiTe, NiO, MgS, MgSe, MgTe, MgO, HgS, HgSe, HgTe, HgO, PbS, PbSe, PbTe, PbO, CuS, CuSe, CuTe, CuO, CoS, CoSe, CoTe, CoO, SrO, SrS, SrSe, CoTe, SrO, FeS, FeSe, FeO, FeTe and combinations of any of these materials.
[0197] More preferably: ZnS, ZnSe, ZnTe, ZnO or a combination of any of these materials.
[0198] In some embodiments of the present invention, the second shell layer comprises at least a first element of group 12 of the periodic table and a second element of group 16 of the periodic table, preferably, the first element is Zn, and the second element is S, Se, O or Te.
[0199] In a preferred embodiment of the present invention, the second shell is represented by the following formula (VII'), ZnS x Se (1-x-z) Te z ,-(VII′),
[0200] Where 0≤x≤1, 0≤z≤1, and x+z≤1, preferably, the shell is ZnSe, ZnS x Se y 、ZnSe y Te z or ZnS x Te z , or ZnS, more preferably ZnSeS or ZnS.
[0201] In some embodiments of the present invention, the shell layer is an alloy shell layer or a gradient shell layer. Preferably, the gradient shell layer is ZnS x Se y 、ZnSe y Te z or ZnS x Te z , more preferably it is ZnS x Se y .
[0202] In some embodiments of the present invention, the concentration of Se in the shell layer varies from a high concentration on the first semiconductor nanoparticle side of the shell layer to a low concentration on the opposite side of the shell layer, more preferably, the concentration of S in the shell layer varies from a low concentration on the first semiconductor nanoparticle side of the shell layer to a higher concentration on the opposite side of the shell layer, and the concentration of Te in the shell layer varies from a high concentration on the first semiconductor nanoparticle side of the shell layer to a lower concentration on the opposite side of the shell layer.
[0203] In some embodiments of the invention, the composition of the second shell layer may be the same as the composition of the outer shell layer.
[0204] In some embodiments of the present invention, the semiconductor light-emitting nanoparticles may further comprise one or more additional outer shell layers as multiple shells disposed on the second shell layer.
[0205] According to the invention, the term "multi-shell" stands for stacked shells consisting of three or more shells.
[0206] In some embodiments of the present invention, in addition to the organic moieties of the present invention, the surface of the semiconductor light emitting nanoparticles may be coated with one or more surface ligands.
[0207] Without wishing to be bound by theory, it is believed that such surface ligands may cause the nano-sized fluorescent material to be more easily dispersed in the solvent.
[0208] Commonly used surface ligands include phosphines and phosphine oxides, such as trioctylphosphine oxide (TOPO), trioctylphosphine (TOP) and tributylphosphine (TBP); phosphonic acids, such as dodecylphosphonic acid (DDPA), tridecylphosphonic acid (TDPA); amines, such as oleylamine, dodecylamine (DDA), tetradecylamine (TDA), hexadecylamine (I) and octadecylamine (ODA), oleylamine (OLA); 1-octadecene (ODE); thiols, such as hexadecylmercaptan, dodecylmercaptan, hexanethiol and polyethylene glycolmercaptan; selenols, wherein the selenol organic part may include a linear or branched alkyl chain that may be saturated or include one or more unsaturated carbon bonds and / or aromatic rings; mercaptocarboxylic acids, such as mercaptopropionic acid and mercaptoundecanoic acid; carboxylic acids, such as oleic acid, stearic acid, myristic acid; acetic acid and any combination of these. In addition, the ligand may include zinc oleate, zinc acetate, zinc myristic acid, zinc stearate, zinc laurate and other zinc carboxylates, sulfonic acids, halides, carbamates.
[0209] Examples of surface ligands have been described, for example, in published International Patent Application No. WO 2012 / 059931A.
[0210] In some embodiments of the invention, the nanoparticles have a full width at half maximum (FWHM) of at most 55 nm measured using a toluene solution at 25°C, preferably, the full width at half maximum (FWHM) is in the range of 30 to 55 nm, more preferably 30 to 47 nm.
[0211] - Determination of the full width at half maximum (FWHM)
[0212] Preferably, the determination of the full width at half maximum (FWHM) is performed using a suitable database preferably comprising at least 10, more preferably at least 20, even more preferably at least 50 data points. The determination is preferably performed using LabVIEW software (LabVIEW 2017; May 2017) with the following VI (virtual instrument):
[0213] 1.'Peak detector for finding the central wavelength and y-values (counts). Preferably the following parameters are used: Width: 10, Threshold: Maximum value of input data divided by 5.
[0214] 2. Divide the counts (y-value) at the center wavelength value (see item 1) by 2 to get the y-value for the half-width of the peak. Find two points with this half-width y-value and take the difference between their two wavelength values to give the FWHM parameter.
[0215] -Quantum yield measurement
[0216] According to the present invention, QY is measured using a Hamamatsu absolute quantum yield spectrometer (model: Quantaurus C11347).
[0217] Preferably, the peak of the maximum emission wavelength of the luminescent nanoparticles is in the range of 350 nm to 3500 nm, preferably 350 nm to 2000 nm, more preferably 400 nm to 800 nm, even more preferably 430 nm to 700 nm.
[0218] - Analysis of nanoparticles, preferably quantum dots (QDs), by GCMS
[0219] According to the present invention, gas chromatography mass spectrometry (GCMS) was performed using an Agilent Technologies 7890B GC system equipped with an autosampler and an Agilent DB-5 column and an MS instrument Agilent Technologies 5977B MSD. The analytes were separated using the following injection method: initial temperature 100°C, maintained at 100°C for 0 minutes; heated to 340°C at a rate of 8°C / min, maintained at 340°C for 15 minutes.
[0220] Samples for GCMS were prepared as follows:
[0221] 3.1 Weigh the starting materials.
[0222] 3.2 Calculate the organic matter content based on TGA measurement.
[0223] 3.3 For every 30 mg of organic component, add 10 ml methanol and 5 ml concentrated hydrochloric acid (caution! exothermic reaction) to dissolve the nanoparticles, preferably quantum dots (QDs). If color still exists, use sonication and Vortex.
[0224] 3.4 Place a magnetic stirrer and heat the solution at 60°C for 20 minutes (do not heat in a closed flask! Make sure the stopper is partially open)
[0225] 3.5 Transfer the solution to a separatory funnel and add toluene (10 ml per 30 mg of organic material).
[0226] 3.6 Extract the aqueous phase and remove the lower aqueous phase.
[0227] 3.7 Add 20 ml of distilled water into the funnel and extract the toluene phase again.
[0228] 3.8 Repeat the extraction of the toluene phase with water at least 3 times or until the aqueous phase has the pH value of distilled water (~5).
[0229] 3.9 Collect the upper phase into a flask containing MgSO4 for at least 30 minutes. Filter the MgSO4 solid.
[0230] 3.10 Transfer the toluene mixture into a GC sample vial for injection.
[0231] -method
[0232] According to the present invention, in one aspect, the method for manufacturing semiconductor nanoparticles, preferably semiconductor luminescent nanoparticles, comprises, essentially consists of or consists of at least the following steps:
[0233] a) mixing at least one semiconductor nanomaterial with another material to obtain a reaction mixture, preferably, the semiconductor nanomaterial comprises at least first semiconductor nanoparticles as cores, and preferably the another material is a solvent;
[0234] (b) forming an outer layer on the semiconductor nanoparticles in the reaction mixture by reacting at least one anion source represented by formula (Va) and / or formula (Vb) with a metal cation precursor in the reaction mixture;
[0235] ABXH (Va)
[0236] ABXXBA (Vb)
[0237] in
[0238] A is an organic group;
[0239] B is a connecting unit connecting A and X;
[0240] H is a hydrogen atom; and
[0241] X is an anion-containing anchoring group capable of forming a monolayer with an added metal cation derived from an added metal cation precursor;
[0242] (c) cooling the reaction mixture from step (b),
[0243] Wherein the reaction mixture in step (b) is maintained at a temperature in the range of 80°C to 200°C, preferably in the range of 100 to 200°C to form the outer layer in step (b).
[0244] As anion source, organic moieties of formula (II'), (III'), (IIIa') or (IV') are preferred,
[0245] L-(U) o -(Y) m -(CH2) n -X 1 (II′)
[0246] in
[0247] L is an organic group, preferably, the organic group is a hydrocarbon group (alkyl, aryl, aralkyl and alkaryl), the heteroaryl group includes aryl, alkaryl, alkyl or aralkyl, alkylamine, fluoroaryl, fluoroalkylaryl, fluoroalkyl, fluoroaralkyl, heteroaryl, the heteroaryl group includes fluoroaryl, fluoroalkylaryl, fluoroalkyl or fluoroaralkyl;
[0248] U is O, CH2 or C=O;
[0249] Y is O, CH2 or C=O;
[0250] n is an integer of 1 or greater;
[0251] m is an integer of 0 or 1 or greater, preferably m is 1;
[0252] o is an integer of 0 or 1 or greater, preferably o is 1;
[0253] X 1 is an anchoring group comprising at least a divalent anion capable of being linked to the metal cation, preferably by a covalent bond, and is selected from Se 2- , S 2- 、Te 2- and O 2- One or more members of
[0254] X 1 -(CH2) a -(OCH2CH2) p -(V) r -(CH2) q -Z (III′)
[0255] X 1 -(CH2) q -(V) r -(OCH2CH2) p -Z (IIIa′)
[0256] in
[0257] X 1 is an anchoring group comprising at least a divalent anion capable of connecting to the metal cation, which is selected from Se 2- , S 2- 、Te 2- and O 2- One or more members of
[0258] V is O, CH2 or C=O;
[0259] Z is a hydrogen atom or an organic group, preferably Z is a hydrogen atom, a straight-chain alkyl group having 1 to 25 carbon atoms, a branched-chain alkyl group having 3 to 25 carbon atoms, -COOH, -SH or -NH2, an alkylamine, a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group, a fluoroaralkyl group, a heteroaryl group, the heteroaryl group includes a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group or a fluoroaralkyl group, preferably Z is a hydrogen atom, a straight-chain alkyl group having 1 to 25 carbon atoms, a branched-chain alkyl group having 3 to 25 carbon atoms, more preferably it is a hydrogen atom, a straight-chain alkyl group having 1-15 carbon atoms, a branched-chain alkyl group having 3-15 carbon atoms, even more preferably it is a hydrogen atom or a straight-chain alkyl group having 1-10 carbon atoms;
[0260] a is an integer of 0 or 1 or greater, preferably 0≤a≤25, more preferably 0≤a≤15, even more preferably 1≤a≤10;
[0261] p is an integer of 0 or 1 or greater, preferably 0≤p≤45, more preferably 0≤p≤25, even more preferably 1≤p≤20, further preferably 4≤p≤18;
[0262] q is an integer of 0 or 1 or more, preferably 0≤q≤25, more preferably 0≤q≤15, even more preferably 0≤q≤10, and further preferably 1≤q≤5;
[0263] r is 0 or integer 1;
[0264] HS-(CH2) a -(OCH2CH2) p -(O) r -(CH2) q -Z′ (IV′)
[0265] wherein a is an integer of 0 or 1 or greater, preferably 0≤a≤25, more preferably 0≤a≤15, even more preferably 1≤a≤10;
[0266] p is an integer of 0 or 1 or greater, preferably 0≤p≤45, more preferably 0≤p≤25, even more preferably 1≤p≤20, further preferably 4≤p≤18;
[0267] q is an integer of 0 or 1 or greater, preferably 0≤q≤25, more preferably 0≤q≤15, even more preferably 0≤q≤10, and further preferably 1;
[0268] Z' is a hydrogen atom, a straight-chain alkyl group having 1 to 25 carbon atoms, a branched-chain alkyl group having 3 to 25 carbon atoms, an alkylamine, a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group, a fluoroaralkyl group, a heteroaryl group, wherein the heteroaryl group includes a fluoroaryl group, a fluoroalkylaryl group, a fluoroalkyl group or a fluoroaralkyl group, preferably Z' is a straight-chain alkyl group having 1 to 25 carbon atoms, a branched-chain alkyl group having 3 to 25 carbon atoms or a hydrogen atom, more preferably a straight-chain alkyl group having 1-15 carbon atoms, a branched-chain alkyl group having 3-15 carbon atoms or a hydrogen atom, and even more preferably a hydrogen atom;
[0269] r is 0 or integer 1;
[0270] For example, the following materials can be preferably used as the anion source.
[0271] SH-CH2-(OCH2CH2)4-O-CH3
[0272] SH-CH2-(OCH2CH2)6-O-CH3
[0273] SH-CH2-(OCH2CH2)8-O-CH3
[0274] SH-(CH2)2-(OCH2CH2)2-O-CH3
[0275] SH-(CH2)2-(OCH2CH2)6-O-CH3
[0276] SH-(CH2)2-(OCH2CH2)8-O-CH3
[0277] SH-(CH2)2-(OCH2CH2)6-CH3
[0278] SH-(CH2)2-(OCH2CH2)6-O-(CH2)2-SH
[0279] SH-(CH2) 7- CH3
[0280] SeH-(CH2) 7- CH3
[0281] SH-(CH2) 11- CH3
[0282] SeH-(CH2) 11- CH3
[0283] SH-(CH2) 17- CH3
[0284] SeH-(CH2) 17- CH3
[0285] SH-(CH2)2-(OCH2CH2)6-O-CH3
[0286] SH-(CH2)2-(OCH2CH2) 16 -O-CH3
[0287] SH-(CH2)2-(OCH2CH2) 17 -O-CH3
[0288] In some embodiments, the organic moiety of the chemical formula (I) or (II) may be an organic moiety represented by the following chemical formula Ia, Ib, Ic, Id, Ie, IIa, IIb, IIc, IId, IIe, IIf, IIg, IIh, IIi or IIj;
[0289]
[0290] Where Y is a divalent bond, m is 0 or 1, R 6 is a hydrogen atom or R 1 , R 7 is a hydrogen atom or R 1 .
[0291] R 1 and R 5 is, at each occurrence, independently or dependently, an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 5 to 12 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, a cycloalkenyl group having 5 to 12 carbon atoms, an aralkyl group having 7 to 15 carbon atoms, a saturated or unsaturated bicyclic or tricyclic hydrocarbon group having 7 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms or said aryl group substituted by an alkyl group, or OR x ;
[0292] R x is an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 5 to 12 carbon atoms, an alkenyl group having 2 to 18 carbon atoms, a cycloalkenyl group having 5 to 12 carbon atoms, an aralkyl group having 7 to 15 carbon atoms, a saturated or unsaturated bicyclic or tricyclic hydrocarbon group having 7 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms, or said aryl group substituted with an alkyl group;
[0293] R2 is a hydrogen atom or R 3 ;
[0294] R a is an alkyl group having 1 to 36 carbon atoms, preferably selected from the group consisting of methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, tetradecyl, hexadecyl, eicosyl, docosyl, pentacosyl, heptacosyl, triacontyl, dotriacontyl, tetratriacontyl, hexatriacontyl and branched chain isomers thereof;
[0295] R 3 is a cycloalkyl group having 5 to 12 carbon atoms, a phenyl group or a naphthyl group which is unsubstituted or substituted with an alkyl group having 1 to 36 carbon atoms, or an aralkyl group having 7 to 9 carbon atoms which is unsubstituted or substituted with an alkyl group having 1 to 36 carbon atoms;
[0296] R 4 is an alkyl group having 1 to 36 carbon atoms, preferably selected from the group consisting of methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, tetradecyl, hexadecyl, eicosyl, docosyl, pentacosyl, heptacosyl, triacontyl, dotriacontyl, tetratriacontyl, hexatriacontyl and branched chain isomers thereof;
[0297] X1 is an anchoring group selected from Se-H (selenol), SH (thiol), Te-H (tellurol) or any combination of these;
[0298] n is zero or an integer;
[0299]
[0300] in
[0301] Z is a divalent bond, preferably selected from a substituted or unsubstituted linear alkylene group having 1 to 10 carbon atoms, a substituted or unsubstituted oxyalkylene group having 1 to 10 carbon atoms,
[0302] Y is the connection unit;
[0303] m is 0 or 1;
[0304] R 6 is a hydrogen atom or R 1 ;
[0305] R 7 is a hydrogen atom or R 1 ;
[0306] R 12 is a hydrogen atom or R 1 ;
[0307] R
[0308] In some embodiments, the organic moiety represented by formula II) is an organic moiety represented by IIa', IIb', IIc', IId', IIe', IIf', IIg', IIh', IIi', or IIj';
[0309]
[0310]
[0311]
[0312] X1 is an anchoring group selected from Se-H (selenol), SH (thiol), Te-H (tellurol), OH (alcohol) or any combination of these;
[0313] n is zero or an integer.
[0314] It is believed that the temperature range of 80° C. to 200° C. is important for forming a crystalline bond between the organic moiety and the outer layer. In other words, by maintaining the reaction temperature in step (b) within this temperature range, the anchoring group of formula (I), (II), (III) and / or (IV) is linked to the cation to form the outer layer, while the organic moiety remains linked to the anchoring group via a covalent bond.
[0315] In a preferred embodiment of the present invention, the implantation of the anion source in step (a) or in step (b) is carried out at a temperature in the range of 0°C to 200°C, preferably in the range of 20°C to 180°C.
[0316] It is believed that the temperature range of the implantation is also important to prevent the XB bond from breaking.
[0317] Preferably, step (b) is performed in the range of 1 minute to 10 hours, preferably 10 minutes to 5 hours, more preferably 20 minutes to 3 hours.
[0318] According to the present invention, preferably, the ratio of the total molar amount of the cationic precursor to the total molar amount of the semiconductor nanoparticles in step (b) is in the range of 20:1 to 200000:1, preferably 100:1 to 60000:1, more preferably 110:1 to 58000:1, even more preferably 120:1 to 5000:1.
[0319] In a preferred embodiment of the present invention, the ratio of the total molar amount of the chalcogen source to the total molar amount of the semiconductor nanoparticles in step (b) is in the range of 20:1 to 200000:1, preferably 100:1 to 60000:1, more preferably 110:1 to 58000:1, even more preferably 120:1 to 5000:1.
[0320] In some embodiments of the present invention, the anion source represented by the chemical formula (2) may be used alone or in combination with any other chalcogen source as the anion source in step (b) to form the outer layer.
[0321] L 1 -U 1 -Y 1 -(CH2) n -Z 1 -Z 2 -(CH2)n -Y 2 -U 2 -L 2 (2)
[0322] L 1 and L 2 Each independently or interdependently is an organic group, preferably, the organic group is a hydrocarbon group (alkyl, aryl, aralkyl and alkaryl), including aryl, alkaryl, alkyl or aralkyl;
[0323] U 1 and U 2 At each occurrence, independently or interdependently, is O, -CH2- or C=O;
[0324] Y 1 and Y 2 At each occurrence, independently or interdependently, is O, -CH2- or C=O;
[0325] n is an integer of 1 or greater;
[0326] Z 1 is a divalent anion selected from Se, S, Te, and O;
[0327] Z 2 It is a divalent anion selected from Se, S, Te, and O.
[0328] In a preferred embodiment of the present invention, the anion source described in formula (2), such as a dichalcogenide, can be used together with a reducing agent in step (b) to form the outer layer. Preferably, the reducing agent is represented by a secondary phosphine.
[0329] In a preferred embodiment of the present invention, the ratio of the total amount of anion source to the total amount of cationic precursor used in step (b) is in the range of 20:1 to 1:20, preferably in the range of 12:1 to 1:12, even more preferably in the range of 5:1 to 1:5.
[0330] - Chalcogen source
[0331] According to the present invention, the term "chalcogen" refers to a chemical element of Group 16 of the Periodic Table, preferably sulfur (S), selenium (Se), oxygen (O) and / or tellurium (Te).
[0332] Therefore, according to the present invention, the term "chalcogen source" refers to a material containing at least one chemical element of the chemical elements of Group 16 of the periodic table, preferably, the chemical element of the chemical elements of Group 16 is oxygen (O), sulfur (S), selenium (Se) and / or tellurium (Te), more preferably sulfur (S) or selenium (Se).
[0333] In a preferred embodiment of the present invention, the chalcogen source is a selenium source, a sulfur source or a combination of a sulfur source and a selenium source. More preferably, it is selected from selenol, diselenide, thiol, disulfide or a combination of these,
[0334] Step (a) – Mixing
[0335] In a preferred embodiment of the present invention, step (a) is carried out under inert conditions, such as under argon (Ar) or N2 conditions, more preferably under Ar conditions.
[0336] In a preferred embodiment of the present invention, the another material used in step (a) is a solvent, more preferably an organic solvent, even more preferably one or more members selected from the group consisting of squalene, squalane, heptadecane, octadecane, octadecene, nonadecane, eicosane, heneicosane, docosane, tricosane, pentacosane, hexacosane, octacosane, nonadecane, triacontan, heneicosane, dotriacontan, tricosane, tetratriacontan, pentatriacontan, hexatriacontan, oleylamine, trioctylamine, ketones, ketone ether acetates such as PGMEA, nitriles, ethers, ether esters, aromatic solvents such as toluene, xylene, ethylbenzene, diethylbenzene, isopropylbenzene, diisopropylbenzene, mesitylene, preferably one or more members selected from the group consisting of squalene, squalane, heptadecane, octadecane, octadecene, nonadecane, eicosane, heneicosane, docosane, tricosane, pentacosane, hexacosane, octacosane, tetracosane , nonacosane, triacontan, hexacontan, dotriacontan, tricaracontan, tetracontan, pentacontan, hexacontan, oleylamine, trioctylamine, ketones, ketone ether acetates such as PGMEA, nitriles, ethers, aromatic solvents such as toluene, xylene, ethylbenzene, diethylbenzene, isopropylbenzene, diisopropylbenzene, mesitylene, more preferably octadecene, oleylamine, squalane, pentacosane, hexacosane, octacosane, nonacosane, trioctylamine or triacontan, ketones, ketones, ether acetates such as PGMEA, nitriles, ethers, ether esters, aromatic solvents such as toluene, xylene, ethylbenzene, diethylbenzene, isopropylbenzene, diisopropylbenzene, mesitylene, even more preferably octadecene, oleylamine, squalane, pentacosane, trioctylamine or hexacosane, tetracosane, ketones, ketone ether acetates such as PGMEA, ether esters, nitriles, ethers, aromatic solvents such as toluene, xylene, ethylbenzene, diethylbenzene, isopropylbenzene, diisopropylbenzene, mesitylene.
[0337] In a preferred embodiment of the present invention, the mixing step is carried out at a temperature in the range of 0 to 100°C, preferably 5 to 60°C, more preferably 10 to 40°C.
[0338] In a preferred embodiment of the present invention, a plurality of first semiconductor nanomaterials may be used in step (a).
[0339] -Semiconductor Nanoparticles
[0340] According to the present invention, the semiconductor nanomaterial comprises, consists essentially of or consists of at least a first semiconductor nanomaterial, except for any ligands attached to the outermost surface of the semiconductor nanoparticle, if attached at all.
[0341] In some embodiments of the present invention, the semiconductor nanoparticles may optionally include one or more shell layers as described above in the "Shell Layer" section, which cover at least a portion of the first semiconductor nanoparticle.
[0342] -The first semiconductor nanomaterial
[0343] According to the present invention, in step (a), several first semiconductor nanomaterials can be used as cores, such as CdS, CdSe, CdTe, ZnS, ZnSe, ZnSeS, ZnTe, ZnO, GaAs, GaP, GaSb, CuS, Cu2S, CuSe, Cu2Se, FeS, FeSe, FeO, FeTe, HgS, HgSe, HgSe, HgTe, InAs, InxGa1-xAs, InP, InP:Zn, InP:ZnS, InP:ZnSe, InP:ZnSSe, InP:Ga or InP:Ga, InSb, InPS, InPZnS, InPSe, InPZn, InPZnSe, InPZnSeS, InPGa, InPG aZn, InP / ZnSe, In / ZnS, InZnP / ZnSe, InP / ZnSeTe, InZnP / ZnSeTe, InGaP / ZnSe, InP / InGaP, InZnP / InGaP, InCdP, InPCdS, InP / ZnSeS, InZnP / ZnSeS, InZnP / ZnS, I nZnP / InGaP / ZnSe, InZnP / InGaP / ZnS, InZnP / InGaP / ZnSeS, InPCdSe, InGaP, InGaPZn, InSb, AlAs, AlP, AlSb, Cu2S, Cu2Se, CuInS2, CuInSe2, CuInZnS, and combinations of any of these.
[0344] In some embodiments, the core is a metal oxide, including, for example, ZnO, FeO, Fe2O3, ZrO2, CuO, SnO, Cu2O, TiO2, WO3, HfO2, In2O3, MgO, Al2O3, and any combination of these.
[0345] In some embodiments, the core comprises a metal such as Au, Ag, W, Pd, Pt, Cu, In, Ti, Zn, Pb, Al, Cd, Zn, and combinations of any of these.
[0346] In some embodiments of the present invention, the first semiconductor nanomaterial contains, consists essentially of, or consists of at least a first element of Group 12 or Group 13 of the periodic table and a second element of Group 15 or Group 16 of the periodic table, preferably, the first element is an element of Group 13 of the periodic table, the second element is an element of Group 15 of the periodic table, more preferably, the first element is In, Ga, or a combination of In and Ga, and the second element is P, except for the ligand attached to the outermost surface of the first semiconductor nanoparticle (if it is attached).
[0347] In a preferred embodiment of the present invention, the first semiconductor nanomaterial may further include an additional element selected from one or more members of Ga, Zn, S and Se.
[0348] In a preferred embodiment of the present invention, the first semiconductor nanomaterial is selected from InP, InP:Zn, InP:ZnS, InP:ZnSe, InP:ZnSSe, InP:Ga or InP:GaZn, InP / ZnSe, InP / ZnS, InP / ZnSeS, InZnP / ZnSe, InZnP / ZnSeS, InZnP / ZnS, InGaP / ZnSe, InP / InGaP, InZnP / InGaP, InZnP / InGaP / ZnSe, InZnP / InGaP / InZnS or InZnP / InGaP / ZnSeS.
[0349] In a preferred embodiment, the first semiconductor nanomaterial is an alloy.
[0350] According to the present invention, the shape type of the first semiconductor nanomaterial of the semiconductor light-emitting nanoparticles and the shape of the semiconductor light-emitting nanoparticles to be synthesized are not particularly limited.
[0351] For example, spherical, elongated, star-shaped, polyhedral, pyramidal, multi-podal such as tetrapodal, tetrahedral, platelet-shaped, cone-shaped and irregular first semiconductor nanoparticles and / or semiconductor light-emitting materials can be synthesized.
[0352] In some embodiments of the present invention, the average diameter of the first semiconductor nanoparticles is in the range of 1 to 20 nm, preferably 1.5 nm to 12 nm.
[0353] Optional step (d) - Shell formation
[0354] According to the present invention, the following step (d) may be optionally applied to further form a shell layer, preferably step (d) is performed before step (b);
[0355] (d) optionally mixing in a solvent at least one semiconductor nanomaterial and / or a first semiconductor nanoparticle (core), preferably the first semiconductor nanoparticle obtained in step (h), and at least a first cationic shell precursor and a first anionic shell precursor to form a shell layer on the first semiconductor material,
[0356] Preferably, said first anion shell precursor is injected into the reaction mixture during step (d).
[0357] In a preferred embodiment of the present invention, preferably, the anion precursor is a chalcogen source, more preferably one or more members selected from trioctylphosphine: Se, tributylphosphine: Se, trioctylphosphine: S, tributylphosphine: S, thiol and selenol.
[0358] Other conditions for forming the shell layer are described in, for example, US Pat. No. 8,679,543 B2 and Chem. Mater. 2015, 27, pp. 4893-4898.
[0359] Nanoparticles can be obtained from public sources or as described in this patent application.
[0360] In a preferred embodiment of the present invention, the cationic shell precursor is a salt of an element of Group 12 of the periodic table, more preferably, the cationic shell precursor is selected from one or more of the following: zinc stearate, zinc myristate, zinc oleate, zinc laurate, zinc palmitate, zinc acetylacetonate, zinc undecylenate, zinc acetate, cadmium stearate, cadmium myristate, cadmium oleate, cadmium laurate, cadmium palmitate, cadmium acetylacetonate, cadmium undecylenate, cadmium acetate, a metal halide represented by chemical formula (XIII) and a metal carboxylate represented by chemical formula (XIV),
[0361] MX 3 n (XIII)
[0362] Where M is Zn 2+ or Cd 2+ , preferably M is Zn 2+ , X 3 Is selected from F - , Cl - Br - and I - The halogen, n is 2,
[0363] [M(O2CR 16 )(O2CR 17 )]-(XIV)
[0364] Where M is Zn 2+ or Cd 2+ , preferably M is Zn 2+ ;
[0365] R 16 is a straight-chain alkyl group having 1 to 30 carbon atoms, a branched-chain alkyl group having 3 to 30 carbon atoms, a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, or a branched-chain unsaturated hydrocarbon group having 3 to 30 carbon atoms. 16 is a straight-chain alkyl group having 1 to 30 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, more preferably, R 16 is a straight-chain alkyl group having 2 to 25 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 6 to 25 carbon atoms, and even more preferably, R 16 is a straight-chain alkyl group having 2 to 20 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 10 to 20 carbon atoms, and preferably, R 16 is a straight-chain alkyl group having 2 to 20 carbon atoms,
[0366] R 17 is a straight-chain alkyl group having 1 to 30 carbon atoms, a branched-chain alkyl group having 3 to 30 carbon atoms, a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, or a branched-chain unsaturated hydrocarbon group having 43 to 30 carbon atoms. 17 is a straight-chain alkyl group having 1 to 30 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, more preferably, R 17 is a straight-chain alkyl group having 2 to 25 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 6 to 25 carbon atoms, and even more preferably, R 17 is a straight-chain alkyl group having 2 to 20 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 10 to 20 carbon atoms, and preferably, R 17 is a straight-chain alkyl group having 2 to 20 carbon atoms.
[0367] In a preferred embodiment, R 16 and R 17 same.
[0368] In a preferred embodiment of the present invention, the ratio of the total amount of the chalcogen source used in step (d) to the total amount of the cationic shell precursor is in the range of 20:1 to 1:20, preferably in the range of 12:1 to 1:12, and the chalcogen source is preferably a selenium source, a sulfur source or a combination of a selenium source and a sulfur source.
[0369] Step (d) can be applied not only to the synthesis of the first shell layer, but also to the synthesis of the second shell layer and / or multiple shell layers.
[0370] – Cooling step (e)
[0371] According to the invention, cooling of the reaction mixture from step (d) is carried out in step (e) after step (d) and before step (b), preferably correspondingly stopping the shell formation reaction.
[0372] As the cooling method, several methods can be used alone or in combination.
[0373] For example, the heat source is removed, a solvent is injected, such as a solvent at room temperature, and / or air cooling is applied.
[0374] In some embodiments, the cooling rate in step (e) may be in the range of 0.03°C / s to 50°C / s, preferably 0.1°C / s to 10°C / s.
[0375] In a preferred embodiment, the reaction mixture is cooled to a temperature below 200°C, more preferably in the range of 200°C to 0°C,
[0376] Step (f) - Mixing step to prepare a second mixture
[0377] In some embodiments of the present invention, the method further comprises step (f), preferably the method comprises step (f) before step (b), more preferably after step (d) and before step (b), even more preferably after step (e) and before step (b).
[0378] (f) mixing the chalcogen source and the cationic precursor with the first semiconductor nanoparticles, optionally with another material, to prepare a second mixture at a temperature ranging from 0°C to 100°C, preferably from 5°C to 60°C, more preferably from 10 to 40°C.
[0379] In some embodiments, as an option, the first semiconductor nanoparticles and the cation source are premixed to prepare a premixed mixture, and then instead of step (f), the chalcogen source is injected into the premixed mixture as step (f") to prepare a second mixture. The same temperature range as described in step (e) can be applied.
[0380] Preferably, the chalcogen source is injected after the cationic shell precursor is injected.
[0381] In some embodiments of the present invention, to obtain semiconductor nanoparticles, the method may optionally include, but is not limited to, the method steps described in the following steps (g) and (h), preferably before step (a);
[0382] (g) preparing first semiconductor nanoparticles in a first mixture by reacting at least one indium precursor and at least one phosphor precursor or by using clusters obtainable by reacting a metal cation precursor with an anion precursor, preferably, the clusters are magic size clusters, the indium precursor is a metal halide represented by the following chemical formula (XV), a metal carboxylate represented by the following chemical formula (XVI), or a combination thereof, the phosphor precursor is an aminophosphine represented by the following chemical formula (XVII), an alkylsilylphosphine such as tris(trimethylsilyl)phosphine, or a combination thereof,
[0383] InV 1 3 (XV)
[0384] Where V 1 Is selected from Cl - Br - and I - of halogen,
[0385] [In(O2CR 3 )3]-(XVI)
[0386] Where R 3 is a straight-chain alkyl group having 1 to 30 carbon atoms, a branched-chain alkyl group having 3 to 30 carbon atoms, a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, or a branched-chain unsaturated hydrocarbon group having 3 to 30 carbon atoms. 3 is a straight-chain alkyl group having 1 to 30 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, more preferably, R 3 is a straight-chain alkyl group having 5 to 25 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 6 to 25 carbon atoms, and even more preferably, R 3 is a straight-chain alkyl group having 10 to 20 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 10 to 20 carbon atoms. 3 is a straight-chain alkyl group having 10 to 20 carbon atoms,
[0387] (R 4 R 5 N)3P (XVII)
[0388] Where R 4 and R 5 is independently or dependently a hydrogen atom or a linear alkyl group having 1 to 25 carbon atoms or a linear unsaturated hydrocarbon group having 2 to 25 carbon atoms at each occurrence, preferably a linear alkyl group having 1 to 10 carbon atoms, more preferably a linear alkyl group having 2 to 4 carbon atoms, even more preferably a linear alkyl group having 2 carbon atoms, optionally, in step (f) a zinc salt and / or a zinc carboxylate is added, preferably the zinc salt is represented by the following chemical formula (XIII), (XIV')
[0389] ZnX 3 n (XIII)
[0390] Where X 3 Is selected from Cl - Br - and I - The halogen, n is 2,
[0391] [Zn(O2CR 1 )(O2CR 2 )]-(XIV′)
[0392] in
[0393] R 1 is a straight-chain alkyl group having 1 to 30 carbon atoms, a branched-chain alkyl group having 3 to 30 carbon atoms, a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, or a branched-chain unsaturated hydrocarbon group having 3 to 30 carbon atoms. 1 is a straight-chain alkyl group having 1 to 30 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, more preferably, R 1 is a straight-chain alkyl group having 5 to 25 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 6 to 25 carbon atoms, and even more preferably, R 1 is a straight-chain alkyl group having 10 to 20 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 10 to 20 carbon atoms. 1 is a straight-chain alkyl group having 10 to 20 carbon atoms,
[0394] R 2 is a straight-chain alkyl group having 1 to 30 carbon atoms, a branched-chain alkyl group having 3 to 30 carbon atoms, a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, or a branched-chain unsaturated hydrocarbon group having 3 to 30 carbon atoms. 2 is a straight-chain alkyl group having 1 to 30 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 2 to 30 carbon atoms, more preferably, R 2 is a straight-chain alkyl group having 5 to 25 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 6 to 25 carbon atoms, and even more preferably, R 2 is a straight-chain alkyl group having 10 to 20 carbon atoms, or a straight-chain unsaturated hydrocarbon group having 10 to 20 carbon atoms. 2 is a straight-chain alkyl group having 10 to 20 carbon atoms,
[0395] R 1 and R 2 Can be the same or different.
[0396] (h) quenching the formation of the first semiconductor nanoparticles by cooling the first mixture in step (f).
[0397] - The cluster used in step (g)
[0398] In some embodiments of the present invention, the first semiconductor nanoparticles in step (g) are prepared in the first mixture by using clusters obtainable by reacting a metal cation precursor with an anion precursor.
[0399] In some embodiments of the present invention, the first semiconductor nanoparticles in step (g) are prepared by using clusters in the first mixture, the clusters are magic size clusters (MSC) selected from InP, InAs, InSb, GaP, GaAs and GaSb, preferably InP magic size clusters (MSC InP), more preferably In 37 P 20 (O2CR4) 51 , wherein the In 37 P 20 (O2CR4) 51 The O2CR4 is -O2CCH2phenyl, or a substituted or unsubstituted fatty acid, such as hexanoate, heptanoate, octanoate, nonanoate, decanoate, undecanoate, dodecanoate, tridecanoate, tetradecanoate, pentadecanoate, hexadecanoate, heptadecanoate, octadecanoate, nonadecanoate or oleate.
[0400] In some embodiments of the present invention, the first semiconductor nanoparticles in step (g) may be optionally prepared by using clusters in the first mixture, and the clusters are magic size clusters (MSCs), but are not limited thereto.
[0401] Preferably, the magic size clusters (MSC) are based on a nanocrystalline core consisting only of fused 6-membered rings with all phosphorus atoms coordinated to four indium atoms in a pseudo-tetrahedral arrangement, preferably with the formula [In 21 P 20 ] 3+ ,[In 42 P 40 ] 6+ ,[In 63 P 60 ] 9+ ,[In 84 P 80 ] 12+ ,[In 95 P 90 ] 15+ ,[In 31 P 30 ] 3+ ,[In 41 P 40 ]3+ ,[In 51 P 50 ] 3+ ,[In 61 P 60 ] 3+ ,[In 71 P 70 ] 3+ ,[In 81 P 80 ] 3+ and / or [In 91 P 90 ] 3+ .
[0402] In some embodiments of the present invention, the first semiconductor nanoparticles in step (g) are prepared by using clusters in the first mixture, and the clusters are magic size clusters (MSCs), wherein the magic size clusters (MSCs) include indium carboxylate ligands, preferably In(O2CR 9 )3, wherein the In(O2CR 9 )3 of the O2CR 9 is -O2CCH2phenyl, or a substituted or unsubstituted fatty acid such as hexanoate, heptanoate, octanoate, nonanoate, decanoate, undecanoate, dodecanoate, tridecanoate, tetradecanoate, pentadecanoate, hexadecanoate, heptadecanoate, octadecanoate, nonadecoate or oleate. Such InP magic size clusters (MSCs) as single source precursors (SSPs) can be prepared as described in D. Gary et al., Chem. Mater., 2015, 27, 1432.
[0403] Step (h) - Quenching step
[0404] According to the present invention, quenching of the formation of the first semiconductor nanoparticles may be accomplished by cooling the reaction mixture.
[0405] As the cooling method, several methods can be used alone or in combination.
[0406] For example, the heat source is removed, a solvent is injected, such as a solvent at room temperature, and / or air cooling is applied.
[0407] In a preferred embodiment of the present invention, the cooling rate in step (h) is in the range of 0.01°C / s to 10°C / s, preferably 0.05°C / s to 6°C / s, more preferably 0.05°C / s to 5°C / s, more preferably 0.1°C / s to 1°C / s, even more preferably 0.2°C / s to 0.7°C / s.
[0408] Step (j) - Surface treatment process
[0409] In some embodiments of the present invention, the method further comprises the following step (j) before step (a), preferably before step (a) and after step (h),
[0410] (j) treating the surface of the first semiconductor nanoparticle with a metal halide represented by the following chemical formula (VIII) or with an alkylammonium halide,
[0411] MX 3 n (VIII)
[0412] Where M is Zn 2+ or Cd 2+ , preferably M is Zn 2+ , X 3 For the selected - , Cl - Br - and I - The halogen of n is 2.
[0413] In some embodiments of the present invention, step (h) is carried out at a temperature in the range of 150°C to 350°C, preferably in the range of 200°C to 320°C, more preferably in the range of 250°C to 300°C, even more preferably in the range of 250°C to 280°C.
[0414] In some embodiments of the present invention, the treatment time of step (j) is in the range of 10 minutes to 10 hours, preferably 20 minutes to 4 hours, more preferably 30 minutes to 3 hours.
[0415] In some embodiments of the present invention, the total molar ratio between the amount of metal halide and the amount of first semiconductor nanoparticles in step (j) is in the range of 500 to 50,000, preferably 1,000 to 20,000, more preferably 1400 to 10,000.
[0416] In some embodiments of the present invention, step (j) is carried out in a solution comprising at least one solvent selected from the group consisting of squalene, squalane, heptadecane, octadecane, octadecene, nonadecane, eicosane, heneicosane, docosane, tricosane, pentacosane, hexacosane, octacosane, nonacosane, triacontan, heneicosane, dotriacontan, tricaracontan, tetratriacontan, pentatriacontan, hexatriacontan, oleylamine, trioctylamine, ketones, ketone ether acetates such as PGMEA, nitriles, ethers, aromatic solvents, preferably squalene, squalane, heptadecane, octadecane, tricosane, pentatriacontan, hexatriacontan, octacosane, nonacosane, triacontan, tritriacontan, dotriacontan, tricaracontan, tetratriacontan, pentatriacontan, hexatriacontan, oleylamine, trioctylamine, ketones, ketone ether acetates such as PGMEA, nitriles, ethers, aromatic solvents, preferably squalene, squalane, heptadecane, octadecane, tricos ... More preferably, octadecane, trioctylamine, oleylamine, squalane, pentacosane, hexacosane, octacosane, nonadecane, eicosane, heneicosane, docosane, tricosane, pentacosane, hexacosane, octacosane, nonadecane, triacontan, triacontan, dotriacontan, tricotriacontan, tetratriacontan, pentatriacontan, hexatriacontan, oleylamine and trioctylamine, more preferably octadecene, trioctylamine, oleylamine, squalane, pentacosane, hexacosane, octacosane, nonadecane, or triacontan, even more preferably octadecene, trioctylamine, oleylamine, squalane, pentacosane, or hexacosane, ketones, ether acetates such as PGMEA.
[0417] In a preferred embodiment of the present invention, each of steps (a) to (j) is carried out under inert conditions, such as under N2 or argon (Ar) conditions, preferably under Ar conditions.
[0418] -Semiconductor Nanoparticles
[0419] In another aspect of the invention, the present invention also relates to semiconductor nanoparticles obtainable or obtained by the method of the present invention.
[0420] In a preferred embodiment, the semiconductor nanoparticles are luminescent nanoparticles.
[0421] - Composition
[0422] On the other hand, the present invention also relates to a composition, which preferably comprises but is not limited to, essentially consists of or consists of at least one nanoparticle of the present invention and at least one additional material, preferably, the nanoparticle is a luminescent nanoparticle of the present invention, preferably, the additional material is selected from organic light-emitting materials, inorganic light-emitting materials, charge transport materials, scattering particles, host materials, nanosized plasma particles, photoinitiators and matrix materials.
[0423] The above-mentioned suitable inorganic luminescent material may be a well-known phosphor, including nanophosphors, quantum size materials, such as those mentioned in Phosphor Handbook, 2nd Edition (CRC Press, 2006), pages 155-338 (WM Yen, S. Shionoya and H. Yamamoto), WO2011 / 147517A, WO2012 / 034625A and WO2010 / 095140A.
[0424] According to the present invention, any type of known materials can be preferably used as the organic light-emitting material and charge transport material, such as well-known organic fluorescent materials, organic host materials, organic dyes, organic electron transport materials, organic metal complexes and organic hole transport materials.
[0425] As examples of scattering particles, it is preferred to use inorganic oxides, such as small particles of SiO2, SnO2, CuO, CoO, Al2O3, TiO2, Fe2O3, Y2O3, ZnO, MgO; organic particles, such as polymerized polystyrene, polymerized PMMA; inorganic hollow oxides, such as hollow silica or any combination of these.
[0426] -Matrix material
[0427] According to the present invention, various known transparent matrix materials suitable for optical devices can be preferably used.
[0428] According to the present invention, the term "transparent" means at least about 60% transmission of incident light at the thickness used in the optical medium and at the wavelength or wavelength range used during operation of the optical medium. Preferably, it exceeds 70%, more preferably, exceeds 75%, and most preferably, exceeds 80%.
[0429] In a preferred embodiment of the present invention, as the matrix material, any type of known transparent matrix material, such as described in WO 2016 / 134820A, can be used.
[0430] In some embodiments of the present invention, the transparent matrix material may be a transparent polymer.
[0431] According to the present invention, the term "polymer" means a material having a repeating unit and having a weight average molecular weight (Mw) of 1000 g / mol or more.
[0432] The molecular weight Mw is determined by means of GPC (=gel permeation chromatography) relative to a polystyrene internal standard.
[0433] In some embodiments of the present invention, the transparent polymer has a glass transition temperature (Tg) of 70° C. or more and 250° C. or less.
[0434] Tg is measured based on the heat capacity change observed in differential scanning colorimetry as described in http: / / pslc.ws / macrog / dsc.htm; Rickey J Seyler, Assignment of the Glass Transition, ASTM publication code number (PCN) 04-012490-50.
[0435] For example, as the transparent polymer for the transparent matrix material, polyacrylate, poly(meth)acrylate, epoxy resin, polyurethane, polysiloxane can be preferably used.
[0436] In a preferred embodiment of the present invention, the weight average molecular weight (Mw) of the polymer as the transparent matrix material is in the range of 1,000 to 300,000 g / mol, more preferably 10,000 to 250,000 g / mol.
[0437] In a preferred embodiment of the present invention, the composition comprises a plurality of luminescent nanoparticles and / or a plurality of semiconductor materials.
[0438] -preparation
[0439] In another aspect, the present invention relates to a formulation comprising, consisting essentially of, or consisting of at least one semiconductor nanoparticle, semiconductor luminescent nanoparticle, or composition of the present invention and at least one solvent.
[0440] Preferably, the solvent is selected from one or more of aromatic hydrocarbons, halogenated hydrocarbons and aliphatic hydrocarbon solvents or alcohols or ethers or ketones or water, more preferably selected from one or more of toluene, xylene, ether, tetrahydrofuran, chloroform, dichloromethane and heptane, purified water, acetate, alcohol, sulfoxide, formamide, nitride, ketone, ether acetate.
[0441] Preferably, the formulation comprises a plurality of luminescent nanoparticles.
[0442] The amount of solvent in the preparation can be freely controlled according to the coating method of the composition. For example, if the composition is to be sprayed, it can contain 90% by weight or more of solvent. In addition, if the slit coating method often used when coating a large substrate is to be carried out, the content of the solvent is generally 60% by weight or more, preferably 70% by weight or more.
[0443] -Use coating
[0444] In another aspect, the present invention relates to the use of semiconductor light-emitting nanoparticles, or semiconductor nanoparticles, or compositions or formulations in electronic devices, optical devices, sensor devices or biomedical devices.
[0445] -Optical media
[0446] In another aspect, the present invention further relates to an optical medium comprising at least one semiconductor nanoparticle, preferably at least one semiconductor luminescent nanoparticle according to the present invention, or a composition or formulation.
[0447] In some embodiments of the present invention, the optical medium may be an optical sheet, such as a color filter, a color conversion film, a remote fluorescent tape, or other film or filter.
[0448] According to the present invention, the term "sheet" includes films and / or layered structure media.
[0449] In some embodiments of the present invention, the optical medium comprises an anode and a cathode, and at least one layer comprising at least one luminescent nanoparticle or composition of the present invention, preferably, the one organic layer is a luminescent layer, more preferably, the medium further comprises one or more additional layers selected from a hole injection layer, a hole transport layer, an electron blocking layer, a hole blocking layer, an electron blocking layer and an electron injection layer.
[0450] According to the present invention, any type of publicly available inorganic and / or organic materials for hole injection layer, hole transport layer, electron blocking layer, light emitting layer, hole blocking layer, electron blocking layer and electron injection layer can be preferably used. For example, as described in WO2018 / 024719 A1, US2016 / 233444 A2, US7754841 B, WO 2004 / 037887 and WO 2010 / 097155.
[0451] In a preferred embodiment of the present invention, the optical medium comprises a plurality of semiconductor luminescent nanoparticles and / or a plurality of semiconductor nanoparticles.
[0452] In some embodiments, the anode and cathode of the optical medium sandwich the organic layer.
[0453] In some embodiments, the additional layers are also sandwiched by the anode and cathode.
[0454] In some embodiments of the present invention, the layer comprises at least one semiconductor nanoparticle of the present invention, preferably a semiconductor light emitting nanoparticle, and a host material, preferably the host material is an organic host material.
[0455] -Optics
[0456] In another aspect, the present invention further relates to an optical device comprising the optical medium.
[0457] In some embodiments of the present invention, the optical device can be a liquid crystal display device (LCD), an organic light emitting diode (OLED), a backlight unit for an optical display, a light emitting diode device (LED), a microelectromechanical system (hereinafter referred to as "MEMS"), an electrowetting display or an electrophoretic display, a lighting device and / or a solar cell.
[0458] Technical Effects
[0459] The present invention provides one or more of the following effects:
[0460] Improvement in particle size distribution, better full width at half maximum (FWHM) value, improved self-absorption value, improvement in absorption per mg of one or more nanoparticles, improvement in quantum yield of nanoparticles, well-controlled shell thickness, improved charge injection capability of nanoparticles, higher device efficiency, reduction in trapped emission of nanoparticles, optimization of surface conditions of the shell portion of the nanoparticles, reduction in lattice defects in the shell layer of the nanoparticles, reduction / prevention of formation of dangling bonds in the shell layer, better thermal stability, better chemical stability, improved chemical stability in one or more desired solvents, improved thermal stability in one or more desired solvents, improved chemical stability in one or more desired matrices, improved thermal stability in one or more desired matrices, improved dispersion in matrices, improved dispersion in solvents, improved hole injection capability into semiconductor light-emitting nanoparticles, improved external quantum efficiency, optimization of the manufacturing process of the nanoparticles, providing new manufacturing processes to improve size control of the nanoparticles, providing new manufacturing processes to better control the kinetics of shell formation, new shell formation processes to achieve well-controlled shell thickness and / or reduce lattice defects in the shell layer, more environmentally friendly and safer manufacturing processes.
[0461] The following Core Synthesis Examples 1 to 2 and Working Examples 1 to 10 provide a description of the present invention, as well as detailed descriptions of their manufacture.
[0462] Working Example
[0463] Core Synthesis Example 1: Synthesis of Magic Size Clusters (MSC)
[0464] Cluster synthesis
[0465] In a 500 mL 4-necked flask, 4.65 g (15.9 mmol) of indium acetate and 13.25 g (58.0 mmol) of myristic acid were weighed in. The flask was equipped with a reflux condenser, a septum, and a tap between the flask and the condenser.
[0466] Place under vacuum at 100° C. for 8 hours and 15 minutes to discharge acetic acid under reduced pressure, and leave overnight at room temperature.
[0467] The next day, the solution was heated again to 100°C and evacuated under these conditions for 1 hour and 45 minutes.
[0468] The total vacuum time at 100°C is 10 hours.
[0469] Pressure: 85mtorr.
[0470] The reaction flask was filled with argon and 100 mL of anhydrous toluene was added. The reaction was heated to 110 °C.
[0471] A mixture of 2.33 mL (2.0 g) of PTMS and 50 mL (43.5 g) of toluene was injected into the flask with indium myristic acid (In(Ma)) at 110°C.
[0472] The formation of MSCs was monitored by UV on timed aliquots taken from the reaction solution. The peak shape (red shift and sharpness) gradually improved.
[0473] When the improvement of peak shape (red shift and sharpness) ceased, a second PTMS solution (1 ml (0.86 g) PTMS in 10.2 ml (8.77 g) toluene) was added in 2 mL portions to achieve the best optical parameters. For example:
[0474] After 13 minutes, add 2 ml of PTMS solution
[0475] After 19 minutes, add 2 ml of PTMS solution
[0476] After 32 minutes, add 2 ml of PTMS solution
[0477] After 44 minutes, the reaction was cooled with a fan and the flask itself was stored in an inert atmosphere.
[0478] result:
[0479] Formation of InP magic size clusters with excitons at 387 nm.
[0480] InP magic size clusters (MSCs) were washed with anhydrous acetonitrile (ratio of crude:acetonitrile was 18:13). The process was repeated with a mixture of anhydrous toluene and acetonitrile in ratios of toluene:acetonitrile of 1.5:1, 1.4:1, 1.75:1. The product was called "magic size clusters (MSCs)".
[0481] Core Synthesis Example 2: Core Synthesis:
[0482] Synthesis of InP Nanoparticles with Exciton Wavelength of 593nm
[0483] A 50 mL, 14 / 20, four-necked round bottom flask equipped with a reflux condenser was evacuated and 10 mL of distilled squalane was injected into it. The apparatus was evacuated with stirring (pressure decreased from 300 mTorr to 200 mTorr in 1 hour) and heated to 375 °C under argon. In the glove box, a 3.15x10 -04 M MSC solution. At 375 ° C, 4 mL (1.26E-06 mol) of this solution was injected into the flask using a 16-gauge needle and a 6 mL syringe;
[0484] After 4 minutes, the cover was removed and the flask was cooled to 200° C. by blowing with a fan. The cover was then replaced and the flask was heated to 265° C.
[0485] More MSCs were added at this time, using the same solution as the initial injection; using a 20 gauge needle and a 3 ml syringe, adding at a rate of 0.7 ml / min at a given time (compared to the initial injection):
[0486] 15 minutes - 0.6 ml (1.89E-07 mol)
[0487] 25 minutes - 0.7 ml (2.21E-07 mol)
[0488] 32 minutes - 0.7 ml
[0489] result:
[0490] InP QDs with excitons at 593 nm were formed.
[0491] Comparative Example 1: Synthesis of ZnSe shell on InP core (trioctylphosphine selenide (TOP-Se) as Se source)
[0492] In this example, the InP core used was synthesized using the core synthesis described above (WO2019 / 224134A) and had a core exciton CWL of 593 nm. The final core solution was washed with a mixture of anhydrous toluene and ethanol (ratio of crude: toluene: ethanol was 1:2:8). The process was repeated with a ratio of crude: toluene: ethanol of 1:2:6. This solution will be further referred to as "SSPInP core".
[0493] Post-synthesis nuclear processing: In a glove box (GB), SSP InP cores (3.5×10 -7 mol) was dissolved with 0.2 ml toluene and transferred to a 50 ml round bottom flask containing 4.8 ml pumped oleylamine (OLAm) and 0.085 g ZnCl2. After a short suction at 50°C to remove the toluene, the flask was filled with argon and heated to 250°C for 30 minutes. The solution was then cooled to 180°C.
[0494] Shell formation process: 2.6 mL of a 0.55 M concentrated solution of Zn(Cl)2 in OLAm and 1 qt (0.72 mL of 2M TOP-Se) anion shell precursor were added to the core treated SSP InP core at 180°C. After 30 minutes, the solution was heated to 200°C. After 30 minutes, the solution was heated to 320°C, 3.2 mL of 0.4 M zinc(II) undecylenate was injected and the reaction was kept at 320°C for 3 hours. After 3 hours at 320°C, the reaction was terminated by cooling the reaction mixture.
[0495] The obtained nanoparticles were washed with a mixture of anhydrous toluene and ethanol (ratio of crude: toluene: ethanol was 3:4:8). The process was repeated. The nanoparticles were then extracted with hexane.
[0496] Comparative Example 2: Synthesis of ZnSeS shell on InP core (trioctylphosphine selenide (TOP-Se) as Se source, dodecanethiol (DDT) as S source)
[0497] This comparative example is similar to comparative example 1, but 0.9 mmol of TOP-Se is injected at 180°C; and 0.56 mmol of DDT is injected at 320°C, 10 minutes after the injection of zinc (II) undecylenate.
[0498] Working Example 1: Synthesis of ZnSe outer layer on InP / ZnSe NPs in ODE with 1-dodecylselenol (DDSe) as Se source
[0499] Synthetic outer layer : At room temperature, the 8.3X10 -8 mol of InP / ZnSe was dissolved with 0.2 ml of toluene and transferred to a 50 ml round bottom flask containing 4 ml of pumped 1-octadecene (ODE). After 30 minutes of pumping at room temperature, 1-dodecyl selenol (0.2 mmol) was added and the flask was heated to 150°C. When the temperature reached 150°C, zinc (II) undecylenate (0.2 mmol) was added and the reaction was kept at 150°C for 1.5 hours. After 1.5 hours at 150°C, the reaction was terminated by cooling the reaction mixture.
[0500] The obtained nanoparticles were washed with a mixture of anhydrous toluene and ethanol (ratio of crude: toluene: ethanol was 3:4:8). The process was repeated. The nanoparticles were then extracted with hexane.
[0501] Table A compares the values of thermal stability, free radical stability, and peroxide stability of the examples and comparative 1.
[0502] Working Example 2: Synthesis of ZnS outer layer on InP / ZnSe NPs in ODE with 1-dodecanethiol as S source
[0503] This working example is similar to working example 1, but uses 1-dodecanethiol as the sulfur precursor.
[0504] Working Example 3: Synthesis of ZnSeS outer layer on InP / ZnSe NPs in ODE with 1-dodecaneselenol as selenium source and 1-dodecanethiol as sulfur source
[0505] This working example is similar to working examples 1 and 2, but 1-dodecane selenol and 1-dodecanethiol are added together in equimolar amounts, keeping the amount of Se+S ions the same as before.
[0506] Working Example 4: Synthesis of ZnSeS outer layer on InP / ZnSe NPs in ODE with 1-dodecaneselenol as Se source and 3-phenylethanethiol as sulfur source
[0507] This working example differs from working example 3 in that 3-phenylethanethiol is used as the sulfur source instead of 1-dodecanethiol.
[0508] Working Example 5: Synthesis of ZnS outer layer on InP / ZnSeS NPs in ODE with 1-dodecanethiol as S source
[0509] This working example is similar to working example 2, but InP / ZnSeS particles are used. InP / ZnSeS is prepared as described in comparative example 2.
[0510] Table A compares the values of thermal stability, free radical stability, and peroxide stability of the examples and comparative 2.
[0511] Working Example 6: Synthesis of ZnS outer layer on InP / ZnSe NPs in ODE with perfluorodecanethiol as S source
[0512] This working example is similar to working example 2, but uses perfluorodecanethiol as the sulfur precursor.
[0513] Table A
[0514]
[0515]
[0516] Thermal stability test - powder thermal test at 150°C in air
[0517] Benzoquinone test - 2.667% wt of p-benzoquinone was added to clean NPs in toluene
[0518] Peroxide test - Add 50%wt of tert-butyl perbenzoate to clean NPs in toluene
[0519] Working Example 7: Experimental Demonstration of DDSe Surface and Crystalline Bonding of QDs from Working Example 1
[0520] Figure 4 The general scheme mentioned in (Scheme 1) describes a multi-step method that was established to characterize the properties between the surface and the crystal-bound ligand (covalently bound ligand), using dodecylselenol (DDSe) as an example.
[0521] 3-Phenylpropylphosphonic acid (PPPA) is known for its stronger affinity for QD surfaces compared to amines, thiols, selenols and carboxylic acids. Surface-bound ligands are desorbed from the QD surface and replaced by PPPA. On the other hand, crystal-bound ligands are integrated into the crystal lattice. Subsequently, their separation from the QDs is impossible without destroying the crystals.
[0522] Characterization of QDs of Working Example 1:
[0523] Figure 1 : QDs from working example 1 before (a) and after (b) addition of PPPA 1 H NMR spectrum (in toluene d8).
[0524] The addition of PPPA resulted in the desorption of DDSe from the QD surface.
[0525] The amount of isolated DDSe (surface bound) (in mmol) was quantified using duroquinone as an external standard. 1 The calculated value from HNMR is 0.00135 mmol, which means that only 1.8 mol% of the total amount of DDSe in the insertion reaction resulted in surface-bound DDSe.
[0526] Figure 2 : QDs after treatment with PPPA and washing with ethanol 1 H NMR spectrum (in toluene d8)
[0527] 1 H NMR showed that the surface-bound DDSe was completely removed from the surface of the QD (signal #2 (Se-H) and signal #3 (CH2-Se) disappeared). However, signal #1 (CH3 of DDSe) still existed. This indicates the existence of a second non-surface-bound DDSe population.
[0528] The QDs were analyzed in GCMS after removal of all surface-bound DDSe. For this purpose, appropriate derivatization was performed using HCl and methanol. This treatment resulted in complete decomposition and dissolution of the QDs.
[0529] Figure 3 : GCMS spectrum of QDs after treatment with PPPA and washing. MS spectrum of the peak with retention time 11.458.
[0530] The sample for GCMS was prepared as described in the embodiment. GCMS confirmed the presence of DDSe. This indicates the crystalline incorporation of DDSe.
[0531] Main conclusions: The QDs from Working Example 1 contain both surface-bound and crystal-bound DDSe.
[0532] Working Example 8: Synthesis of ZnS outer layer on InP-based red quantum dots in PGMEA with poly(ethylene glycol) methyl ether thiol Mn 800 (mPEG800-SH) as S source
[0533] 183.5 mg (1 mmol) Zn(OAc)2 was weighed into a 50 mL round-bottom four-necked reaction flask, placed under vacuum for 40 minutes, placed under argon, and introduced into a glove box; 6 mL of PGMEA and 0.61 mL of InP-based red quantum material (QM) were added.
[0534] Observation - Red suspension.
[0535] Place under vacuum at room temperature for 20 minutes.
[0536] Place under Ar.
[0537] 2 mL of PGMEA was added.
[0538] Heat (8 min) to 144°C (reflux, condenser cooled with water flow).
[0539] Inject 1.15 mL of a 0.43 M solution of mPEG-SH in PGMEA at 144°C - t = 0
[0540] Maintain at 144°C for 65 minutes.
[0541] 1.15 mL of a 0.43 M solution of mPEG-SH in PGMEA was injected.
[0542] Keep at 144°C for 70 minutes. End. Total - 2 hours 15 minutes at 144°C.
[0543] The obtained QDs were washed with anhydrous hexane (ratio of crude:hexane 1:1). The process was repeated with a mixture of anhydrous PGMEA:hexane 1:1. The QDs were then extracted with toluene.
[0544] Table B:
[0545]
[0546]
[0547] Table B compares the thermal stability values of the described working example 8 and the first semiconductor material used (a red quantum material based on InP).
[0548] Working Example 9: Synthesis of ZnS outer layer on InP-based red quantum dots in PGMEA with poly(ethylene glycol) methyl ether thiol Mn 800 (mPEG800-SH) as S source
[0549] 1.28 g of zinc acetate (Zn(OAc)2) was weighed into a 250 ml round bottom flask and degassed at 200 mTorr for 25 minutes while stirring. Place under Ar atmosphere. Insert into glove box.
[0550] Add 56 ml of 2.1 gr of InP based red quantum material PGMEA and toluene solution. Install the mixture on a Schlenk line. Place under Ar. Install a distillation apparatus and distill off toluene.
[0551] The flask was heated to reflux and injected with 7.7 ml of 0.4 M mPEG800-SH PGMEA solution.
[0552] After 65 minutes, another 7.7 ml of 0.4 M mPEG800-SH PGMEA solution was injected.
[0553] After refluxing for an additional 70 minutes the flask was cooled to room temperature (total reaction time 2 hours 15 minutes).
[0554] The resulting QDs were cleaned as follows: solids were removed by centrifugation; QDs were precipitated with anhydrous hexane (1:1 crude:hexane ratio); the process was repeated with a 1:1 mixture of anhydrous PGMEA:hexane and then twice with a 2:3 mixture of anhydrous toluene:hexane.
[0555] Table C:
[0556]
[0557] Table C compares the thermal stability values of the described working example 9 with a reference material which was prepared similarly to working example 9 but without the Zn(OAc)2.
[0558] Working Example 10: Synthesis of ZnS outer layer on InP-based green quantum material with core-shell structure in diisopropylbenzene with poly(ethylene glycol) methyl ether thiol Mn 350 (mPEG350-SH) as S source
[0559] Weigh 0.215 g Zn(OAc)2 outside the GB into a 50 ml round-bottom flask and introduce the flask into the GB. Add 8 ml diisopropylbenzene (DIPB) and then add 270 mg of a toluene solution of InP-based green quantum dots. Mount the mixture on a Schlenk line and remove toluene under reduced pressure. Fill the flask with Ar. Heat the flask to 160°C and inject 1.3 ml of a 0.9 M solution of mPEG(350)-SH in diisopropylbenzene. After 90 minutes at 160°C, the reaction is cooled to ambient temperature. QDs precipitate when cooled below 50°C. Add toluene (6 mL) to dissolve the quantum dots.
[0560] The obtained QDs were washed as follows: the solids were removed by centrifugation; the QDs were precipitated with anhydrous heptane ((crude + toluene): heptane ratio was 1:1), and the process was repeated with anhydrous PGMEA:heptane mixture of 1:2 and then anhydrous toluene:heptane mixture of 1:1.
Claims
1. Semiconductor nanoparticles comprising nuclear; an outer layer comprising metal cations and divalent anions covering at least a portion of the core; and one or more types of organic moieties directly linked to the anion of the outer shell by covalent bonds, Wherein the divalent anion is selected from Se 2- , S 2- 、Te 2- , O 2- or any combination of these, wherein the metal cation is selected from Zn 2+ 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ A divalent cation, or selected from Ti 4+ ,Ge 4+ 、Si 4+ 、Zr 4+ , Hf 4+ and Sn 4+ of tetravalent cations; The organic part is represented by the following chemical formula (III) or (III'); *-(CH2) a -(OCH2CH2) p -(V) r -(CH2) q -Z (III) *-(CH2) q -(V) r -(OCH2CH2) p -Z (III´) in V is O, CH2 or C=O; Z is a hydrogen atom, a straight chain alkyl group having 1 to 25 carbon atoms, or a branched chain alkyl group having 3 to 25 carbon atoms; a is an integer of 0 or 1 or greater; p is an integer of 1 or greater; q is an integer of 0 or 1 or greater; r is 0 or integer 1; The "*" represents the point of attachment to the anion in the outer shell. 2 . The nanoparticle according to claim 1 , wherein Z is a hydrogen atom, a linear alkyl group having 1 to 15 carbon atoms, or a branched alkyl group having 3 to 15 carbon atoms. The nanoparticle according to claim 1 , wherein Z is a hydrogen atom or a linear alkyl group having 1 to 10 carbon atoms.
4. The nanoparticle according to claim 1, wherein the organic portion is represented by the following chemical formula (IV): *-(CH2) a -(OCH2CH2) p -(O) r -(CH2) q -Z´ (IV) Where a is an integer of 0 or 1 or greater; p is an integer of 1 or greater; q is an integer of 0 or 1 or greater; Z' is a hydrogen atom, a straight chain alkyl group having 1 to 25 carbon atoms, or a branched chain alkyl group having 3 to 25 carbon atoms; r is 0 or integer 1; "*" indicates the connection point to the anion in the outer shell, connected to the S atom or Se atom in the outer shell. The nanoparticle according to claim 4 , wherein Z is a hydrogen atom, a linear alkyl group having 1 to 15 carbon atoms, or a branched alkyl group having 3 to 15 carbon atoms. The nanoparticle according to claim 4 , wherein Z is a hydrogen atom, a linear alkyl group having 1 to 10 carbon atoms.
7. The nanoparticle according to claim 1 or 4, wherein 1≤p≤45. The nanoparticle according to claim 1 , wherein 1≤p≤25.
9. The nanoparticle of claim 1 or 4, wherein the organic moiety is covalently bound to anions in the outer layer of the inorganic lattice which are not removed by ligand exchange.
10. The nanoparticle according to claim 1 or 4, wherein the metal cation is a transition metal of Group 12 or Group 14 selected from Zn 2+ , Hg 2+ or Pb 2+ One or more of .
11. A method for producing semiconductor nanoparticles, comprising at least the following steps: (a) mixing at least one semiconductor nanoparticle with another material to obtain a reaction mixture, wherein the semiconductor nanoparticle comprises at least a first semiconductor nanoparticle as a core, and the other material is a solvent; (b) forming an outer layer on semiconductor nanoparticles in the reaction mixture by reacting at least one anion source represented by formula (III'') or (IIIa') with a metal cation precursor in the reaction mixture; X 1 -(CH2) a -(OCH2CH2) p -(V) r -(CH2) q -Z (III’’) X 1 -(CH2) q -(V) r -(OCH2CH2) p -Z (IIIa´) The metal cation is selected from Zn 2+ 、Ni 2+ 、Co 2+ , Ca 2+ , Sr 2+ , Hg 2+ Mg 2+ and Pb 2+ A divalent cation, or selected from Ti 4+ ,Ge 4+ 、Si 4+ 、Zr 4+ , Hf 4+ and Sn 4+ of tetravalent cations; in X 1 is an anchoring group comprising at least a divalent anion capable of connecting to the metal cation, which is selected from Se 2- , S 2- 、Te 2- and O 2- One or more members of V is O, CH2 or C=O; Z is a hydrogen atom, a straight chain alkyl group having 1 to 25 carbon atoms, or a branched chain alkyl group having 3 to 25 carbon atoms; a is an integer of 0 or 1 or greater; p is an integer of 1 or greater; q is an integer of 0 or 1 or greater; r is 0 or integer 1; (c) cooling the reaction mixture from step (b), wherein the reaction mixture in step (b) is maintained at a temperature in the range of 80°C to 200°C to form the outer layer in step (b).
12. The method according to claim 11, wherein in step (b), the implantation of the anion source is performed at a temperature in the range of 0°C to 200°C.
13. The method according to claim 11 or 12, wherein step (b) is performed in the range of 1 minute to 10 hours.
14. The method according to claim 11 or 12, wherein the ratio of the total molar amount of the cationic precursor to the total molar amount of the semiconductor nanoparticles in step (b) is in the range of 20:1 to 200000:
1.
15. The method according to claim 11 or 12, wherein the anion source is used in step (b) together with a reducing agent to form the outer layer, the reducing agent being represented by a secondary phosphine.
16. The method according to claim 11 or 12, wherein the molar ratio of the total amount of the anion source to the total amount of the cationic precursor used in step (b) is in the range of 20:1 to 1:
20.
17. The method according to claim 11 or 12, wherein the anion source is also represented by chemical formula (IV'): HS-(CH2) a -(OCH2CH2) p -(O) r -(CH2) q -Z´ (IV´) Where a is an integer of 0 or 1 or greater; p is an integer of 1 or greater; q is an integer of 0 or 1 or greater; Z' is a hydrogen atom, a straight chain alkyl group having 1 to 25 carbon atoms, or a branched chain alkyl group having 3 to 25 carbon atoms; r is 0 or integer 1.
18. Semiconductor nanoparticles obtained by the method according to any one of claims 11 to 17.
19. A composition comprising at least one semiconductor nanoparticle according to any one of claims 1 to 10 and 18, and at least one additional material selected from the group consisting of organic light-emitting materials, inorganic light-emitting materials, charge transport materials, scattering particles, host materials, nano-sized plasma particles, photoinitiators and matrix materials.
20. A formulation comprising at least one semiconductor nanoparticle according to any one of claims 1 to 10, 18 or a composition according to claim 19, and at least one solvent selected from one or more of aromatic hydrocarbon solvents, halogenated hydrocarbon solvents and aliphatic hydrocarbon solvents, ethers, esters, ionic liquids, alcohols and water.
21. Use of the semiconductor nanoparticles according to any one of claims 1 to 10, 18, or the composition according to claim 19, or the preparation according to claim 20 in electronic devices, optical devices, sensor devices or biomedical devices.
22. An optical medium comprising at least one semiconductor nanoparticle according to any one of claims 1 to 10, 18 or a composition according to claim 19, or a formulation according to claim 20.
23. An optical medium according to claim 22, comprising an anode and a cathode, and at least one layer comprising at least one semiconductor nanoparticle according to any one of claims 1 to 10, 18 or a composition according to claim 19, the medium further comprising one or more layers selected from a hole injection layer, a hole transport layer, an electron blocking layer, a hole blocking layer, an electron blocking layer and an electron injection layer.
24. An optical medium according to claim 22 or 23, wherein the layer comprises at least one semiconductor nanoparticle according to any one of claims 1 to 10, 18 and a host material, the host material being an organic host material.
25. An optical device comprising the optical medium according to any one of claims 22 to 24.
Citation Information
Patent Citations
Polycyclic phenylpyridine iridium complexes and derivatives thereof for oleds
US20160233444A1
Polymer
US7754841B2
Stable indium-containing semiconductor nanocrystals
US8679543B2
Device with embedded flash and eeprom memories
WO2000058969A1
Conjugated polymers containing arylamine units, the representation thereof and the use of the same
WO2004037887A2